Oxygen absorbing laminate used for paper container for liquid

JP2024169656A5Active Publication Date: 2025-04-04DAI NIPPON PRINTING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024165940
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-04-04
Estimated Expiration
2040-07-06

AI Technical Summary

Technical Problem

Existing packaging materials for liquids lack effective oxygen barrier properties, leading to content deterioration and aroma loss, while also posing issues of odor generation, increased costs, and waste management challenges.

Method used

A laminate structure comprising a paper base layer, an oxygen barrier layer, an oxygen-absorbing adhesive layer, and a sealant layer, with optional reinforcing and functional layers, utilizing an oxygen-absorbing adhesive composition containing an oxygen-absorbing compound and an oxidation-promoting catalyst, which absorbs oxygen and suppresses its permeation.

Benefits of technology

The laminate effectively reduces oxygen concentration, prevents content deterioration, maintains aroma, and enhances sealability, while reducing packaging costs and waste, without the need for additional oxygen absorbers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

PURPOSE: To provide a laminate used for a paper container for liquid, which has less generated odor and excellent barrier property to oxygen gas, absorbs oxygen in a content storage space to reduce the oxygen concentration and inhibits oxygen-induced deterioration of the content and has excellent balance of heat sealability, low odor property, low oxygen concentration, aroma retention, content resistance and filling and packaging properties, and to provide a packaging material and a paper container for liquid prepared using the laminate.SOLUTION: There is provided an oxygen absorbing laminate for a paper package used to prepare a paper package for liquid, which includes a layer structure obtained by laminating at least a paper base material layer, an oxygen barrier layer, an oxygen-absorbing adhesive layer and a sealant layer in this order, wherein the oxygen-absorbing adhesive layer is a layer formed from a specific oxygen-absorbing adhesive composition, and the oxygen-absorbing adhesive composition contains at least an oxygen absorbing compound and an oxidation accelerating catalyst.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an oxygen-absorbing laminate for use in paper containers for liquids which produces little odor, has barrier properties against external oxygen gas and absorbs oxygen within a content storage space to suppress oxygen-induced deterioration of the contents, has an excellent balance of aroma retention, content resistance, and heat sealability, and is suitable for filled packaging, and also relates to an oxygen-absorbing packaging material and an oxygen-absorbing paper container made from the oxygen-absorbing laminate. [Background technology]

[0002] Conventional packaging methods for preventing the deterioration of the quality of contents, such as food, medical products, chemical products, and cosmetics, due to oxygen have included using packaging materials with high oxygen barrier properties, replacing the gas in the content storage area with an inert gas such as nitrogen gas, and including an oxygen scavenger packaged with reduced iron powder or the like. However, these have problems such as insufficient performance, increased packaging costs, increased waste, only functioning in moist environments, and the risk of accidental ingestion. Furthermore, Patent Document 1 describes a packaging material that uses a resin that has oxygen absorbing properties and emits little odor. However, this resin is polycyclododecene, which is insoluble in polar solvents and has no active hydrogen groups, and is therefore unsuitable as an adhesive raw material for packaging materials made of laminates. Furthermore, Patent Document 2 describes a laminating adhesive made of a resin using methyltetrahydrophthalic acid as a raw material having oxygen absorbing properties, but this adhesive has the drawback of being unstable due to its low oxygen absorbing properties. Patent Document 3 describes an oxygen-absorbing resin that is a thermoplastic resin having a repeating unit composed of a saturated five-membered ring having a substituent that contains a carbon-carbon double bond and a -CH=CH- group linking the saturated five-membered rings. However, this resin has drawbacks such as being difficult to use due to its poor solubility in solvents and emitting a strong odor. Disclosed gas barrier packaging materials containing a paper base material include those having a gas barrier layer made of a water-soluble polymer and an inorganic layered compound on a paper base material (hereinafter also referred to as "base paper") (Patent Documents 4 and 5), and those having a barrier layer made of a specific vinyl alcohol-based polymer on a coating layer (Patent Documents 5 and 6). Disclosed water vapor barrier packaging materials containing a paper base material include packaging paper having a moisture-proof layer made of synthetic resin latex, wax, and inorganic fine particles (Patent Document 7). However, packaging materials in which a resin with gas barrier properties and a resin with water vapor barrier properties are laminated or pasted onto a paper base material (base paper) have limitations on the types of resin that can be laminated, and therefore have the problem of being unable to meet various quality requirements. On the other hand, packaging materials that have been given gas barrier and water vapor barrier properties by coating a paper substrate (base paper) with a resin having gas barrier properties and a resin having water vapor barrier properties have few restrictions on the types of resins that can be used, making it possible to meet various quality requirements. However, when a moisture-proof layer of Patent Document 7 is provided on a packaging material that has both gas barrier and water vapor barrier properties, for example, a packaging material having gas barrier properties of Patent Document 4 or Patent Document 5, there is a problem that good water vapor barrier properties are obtained but gas barrier properties are not obtained. Also, even when a gas barrier layer of Patent Document 4 or Patent Document 5 is provided on a moisture-proof paper having a water vapor barrier layer of Patent Document 7, sufficient gas barrier properties and water vapor barrier properties cannot be achieved at the same time. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 5873770 [Patent Document 2] Patent No. 5671816 [Patent Document 3] Patent No. 6505699 [Patent Document 4] JP 2009-184138 A [Patent Document 5] JP 2003-094574 A [Patent Document 6] Patent No. 5331265 [Patent Document 7] JP 2005-162213 A Summary of the Invention [Problem to be solved by the invention]

[0004] The object of the present invention is to provide a laminate for use in paper containers for liquids which generates little odor, has excellent barrier properties against oxygen gas, absorbs oxygen in the content storage space to reduce the oxygen concentration and suppresses deterioration of the contents due to oxygen, and has an excellent balance of heat sealability, low odor, low oxygen concentration, aroma retention, content resistance, and filling and packaging properties, and to provide a packaging material and a paper container for liquids made using the laminate. [Means for solving the problem]

[0005] In order to solve the above problems, the inventors have discovered that a laminate including a layer structure in which at least a paper base layer, an oxygen barrier layer, an oxygen-absorbing adhesive layer, and a sealant layer are laminated in this order can solve the above problems. That is, the present invention is characterized in the following points. 1. An oxygen-absorbing laminate for a paper container for producing a liquid paper container, comprising a layer structure in which at least a paper base layer, an oxygen barrier layer, an oxygen-absorbing adhesive layer, and a sealant layer are laminated in this order, The oxygen-absorbing adhesive layer is a layer formed from an oxygen-absorbing adhesive composition, The oxygen-absorbing adhesive composition contains at least an oxygen-absorbing compound and an oxidation-promoting catalyst, The oxygen absorbing compound has one or more unsaturated five-membered rings, any bond between the five carbon atoms constituting the unsaturated five-membered ring is a carbon-carbon double bond; A monovalent and / or divalent or higher electron-donating organic group 1 is bonded to the unsaturated five-membered ring; When the number of the unsaturated five-membered ring is one, the five-membered ring or the organic group 1 has a functional group having an active hydrogen or a group in which the active hydrogen of the functional group having an active hydrogen is substituted with a monovalent organic group 2, When the number of the unsaturated five-membered rings is two or more, the unsaturated five-membered rings are bonded to each other via a divalent or higher organic group 2 which substitutes an active hydrogen of an active hydrogen group on each of the five-membered rings or the organic group 1. Oxygen absorbing laminate for paper containers. 2. A reinforcing layer is further provided between the oxygen absorbing adhesive layer and the sealant layer. 2. The oxygen-absorbing laminate for a paper container according to 1 above. 3. The paper base layer includes a coating resin layer on the surface. 3. The oxygen-absorbing laminate for a paper container according to 1 or 2 above. 4. The structure of the unsaturated five-membered ring, or the structure consisting of the unsaturated five-membered ring and organic group 1, is derived from one or more members selected from the group consisting of cyclopentadiene, dicyclopentadiene, norbornene, and derivatives thereof. 4. The oxygen-absorbing laminate for a paper container according to any one of 1 to 3 above. 5. The organic group 2 includes a structural portion derived from an isocyanate compound, or an isocyanate compound and a hydroxyl group-containing compound. 5. The oxygen-absorbing laminate for a paper container according to any one of 1 to 4 above. 6. The isocyanate compound is xylene diisocyanate, hexamethylene diisocyanate, one or more selected from the group consisting of isocyanate, isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, and derivatives thereof; 6. The oxygen-absorbing laminate for a paper container according to 5 above. 7. The hydroxyl group-containing compound is one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof. 7. The oxygen-absorbing laminate for a paper container according to 5 or 6 above. 8. The organic group 2 does not have a crosslinkable functional group. 8. The oxygen-absorbing laminate for a paper container according to any one of 1 to 7 above. 9. The organic group 2 has one or more crosslinkable functional groups, the crosslinkable functional group is a hydroxyl group and / or an isocyanate group; 8. The oxygen-absorbing laminate for a paper container according to any one of 1 to 7 above. 10. The oxygen-absorbing compound contains one or more compounds selected from the group consisting of compounds represented by the following formulas (1) to (4): 8. The oxygen-absorbing laminate for a paper container according to any one of 1 to 7 above. [ka] [ka] [ka] [ka] (In the formula, a to e are each a number of 1 or more, and R 1 , R 2 , R 3 Each of the is an organic group having one or more carbon atoms, contains at least an alkylene and / or phenylene structure, and further contains a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof. 11. The oxygen-absorbing compound contains a compound represented by the following formula (5): 8. The oxygen-absorbing laminate for a paper container according to any one of 1 to 7 above. [ka] (In the formula, f is a number equal to or greater than 0, and R 4 and R 5 Each of the above is an organic group having one or more carbon atoms, containing at least an alkylene and / or phenylene structure, and further may contain a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof. 12. The oxidation-promoting catalyst is a peroxide or a compound containing a cation consisting of a transition metal; 12. The oxygen-absorbing laminate for a paper container according to any one of 1 to 11 above. 13. The compound containing a cation made of a transition metal is a metal soap made of a transition metal compound capable of releasing a cation or complex made of a transition metal and an anion or ligand made of a fatty acid. 12. The oxygen-absorbing laminate for a paper container according to any one of 1 to 11 above. 14. The oxygen absorbing adhesive composition further contains a modifier, 14. The oxygen-absorbing laminate for paper containers according to any one of 1 to 13 above, wherein the modifying agent contains an isocyanate compound and / or a hydroxyl group-containing compound. 15. The isocyanate compound is one or more selected from the group consisting of xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, and derivatives thereof. 15. The oxygen-absorbing laminate for a paper container according to 14 above. 16. The hydroxyl group-containing compound includes one or more selected from the group consisting of polyester polyols, poly(meth)acrylic acid ester polyols, polyalkylene ether diols, and urethane chain-extended polyols thereof. 15. The oxygen-absorbing laminate for a paper container according to 13 or 14 above. 17. An oxygen-absorbing packaging material for paper containers, produced using the oxygen-absorbing laminate for paper containers described in any one of 1 to 16 above. 18. An oxygen-absorbing paper container for liquids, which is produced using the oxygen-absorbing packaging material for paper containers described in 17 above, The oxygen barrier layer is a layer located outside the oxygen absorbing adhesive layer. Oxygen absorbing paper container for liquids. Effect of the Invention

[0006] According to the present invention, it is possible to obtain a laminate for use in paper containers for liquids which generates little odor, has excellent barrier properties against oxygen gas, absorbs oxygen in the content storage space to reduce the oxygen concentration and suppress deterioration of the contents due to oxygen, and has an excellent balance of heat sealing properties, low odor properties, low oxygen concentration properties, aroma retention properties, content resistance, and filling and packaging properties, as well as a packaging material and a paper container for liquids made using the laminate. Furthermore, packaging materials made from the laminate of the present invention are particularly suitable for flexible packaging applications, shortening the packaging process, reducing costs, and making the package lighter. Since the package does not require the inclusion of an oxygen absorber as was previously included, this eliminates the risk of the oxygen absorber being accidentally ingested and reduces the amount of waste consisting of the oxygen absorber. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 is a cross-sectional view showing one example of the layer structure of an oxygen-absorbing laminate for paper containers of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing another example of the layer structure of the oxygen-absorbing laminate for paper containers of the present invention. [Diagram 3] FIG. 1 is a perspective view showing an example of an oxygen-absorbing paper container of the present invention. [Figure 4] FIG. 4 is a front view showing a blank plate used in manufacturing the oxygen-absorbing paper container shown in FIG. 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present invention will be described in more detail below. The following description of the constituent elements is an example of an embodiment of the present invention, and the present invention is not limited to these contents as long as it does not exceed the gist of the present invention. In the present invention, the terms film and sheet have the same meaning.

[0009] <Oxygen-absorbing laminate for paper containers> The oxygen-absorbing laminate for paper containers of the present invention is a laminate used for paper containers for liquids, and includes at least a layer structure including a paper base layer, an oxygen barrier layer, an oxygen-absorbing adhesive layer, and a sealant layer laminated in this order. It is preferable that the laminate further includes a reinforcing layer between the oxygen-absorbing adhesive layer and the sealant layer. When forming an oxygen-absorbing paper container for liquids (hereinafter sometimes abbreviated as liquid paper container or oxygen-absorbing paper container) using an oxygen-absorbing packaging material for paper containers (hereinafter sometimes abbreviated as oxygen-absorbing packaging material) made from an oxygen-absorbing laminate for paper containers (hereinafter sometimes abbreviated as oxygen-absorbing laminate), the sealant layer is heat-sealed, and the oxygen barrier layer is located outside the oxygen-absorbing paper container for liquids rather than the oxygen-absorbing adhesive layer. By positioning the oxygen barrier layer outside the oxygen-absorbing adhesive layer, the amount of oxygen passing through the oxygen-absorbing paper container for liquids from the outside is reduced, and the efficiency with which the oxygen-absorbing adhesive layer absorbs oxygen in the content storage space and reduces the oxygen concentration is increased.

[0010] The oxygen-absorbing laminate for a paper container can contain layers having various other functions, as necessary. For example, it may have other base material layers or printed layers, and may include reinforcing layers to satisfy various conditions such as deformation resistance, drop impact resistance, pinhole resistance, heat resistance, sealability, quality maintenance, workability, hygiene, and the like. In addition, the packaging material may have a functional layer for improving the oxygen gas barrier property, imparting barrier properties against water vapor and the like, imparting aroma retention to the contents to be filled and packaged, and preventing the contents from having an unpleasant taste or odor. Furthermore, between or within each of the above layers, an adhesive resin layer may be included to improve interlayer adhesion.

[0011] [Contents] In the above, the contents are liquids, and examples thereof include beverages, alcoholic beverages such as sake and wine, soups, seasonings, shampoos, cosmetics, and the like.

[0012] <Each layer constituting the oxygen-absorbing laminate for paper containers> <Oxygen barrier layer> The oxygen barrier layer is a layer in an oxygen-absorbing paper container for liquids made from an oxygen-absorbing laminate for paper containers that suppresses oxygen transmission through the oxygen-absorbing paper container for liquids from the outside of the oxygen-absorbing paper container for liquids to the internal content storage section. In an oxygen-absorbing paper container for liquids, the oxygen barrier layer is positioned outside the oxygen-absorbing adhesive layer to suppress the transmission of oxygen from outside the oxygen-absorbing paper container for liquids, thereby enhancing the effect of the oxygen-absorbing adhesive layer absorbing oxygen in the content storage section of the oxygen-absorbing paper container for liquids and reducing the oxygen concentration. The oxygen barrier layer can be made of various oxygen barrier materials. In addition, the oxygen barrier layer may be made of an oxygen barrier material that has gas barrier properties not only against oxygen but also against water vapor, light blocking properties against sunlight, aroma retention properties for the contents, etc. In addition, a barrier material that has gas barrier properties against water vapor, light blocking properties against sunlight, aroma retention properties for the contents, etc. may be used in combination.

[0013] Specifically, the oxygen barrier material may be one or more selected from the group consisting of metal foil, resin film with an inorganic vapor deposition layer, and resin coating film or film made of an oxygen barrier resin. Examples of inorganic compounds in the inorganic vapor deposition layer include metals, metal oxides, metal nitrides, and metal carbides. Among the above, resin films with a metal vapor deposition layer, resin films with a metal oxide vapor deposition layer, and resin coating films or resin films made of barrier resins are particularly preferred, as they have excellent barrier properties against oxygen gas, water vapor, light blocking, aroma retention, etc., and are environmentally friendly in terms of disposal of the container.

[0014] A specific example of the metal foil is aluminum foil, which has a thickness of preferably 4 μm to 40 μm, more preferably 6 μm or more and 12 μm or less, and even more preferably 7 μm or more and 9 μm or less. Specific examples of metal elements constituting the above inorganic compounds include aluminum (Al), silicon (Si), magnesium (Mg), calcium (Ca), potassium (K), tin (Sn), sodium (Na), boron (B), titanium (Ti), lead (Pb), zirconium (Zr), yttrium (Y), zinc (Zn), vanadium (V), barium (Ba), and chromium (Cr).

[0015] Specific examples of inorganic compounds include metals, metal oxides, metal nitrides, and metal carbides made of the above-mentioned metal elements. In addition, indium tin oxide (ITO), SiO x C y Also included are composite inorganic compounds such as membranes. Specific examples of the inorganic compound of the inorganic vapor deposition layer include silicon nitride, silicon carbide, etc. Among these, silica and alumina are preferable.

[0016] The average composition of an inorganic compound is expressed as, for example, SiO x , AlO x , SiO x C y MO x , M.O. x C y (In the formula, M represents a metal element, and the values ​​of x and y depend on the metal element. The range of X is different for each.) In the case of metal oxides, the value of X can range from 0 to 2 for silicon, 0 to 1.5 for aluminum, 0 to 1 for magnesium, 0 to 1 for calcium, 0 to 0.5 for potassium, 0 to 2 for tin, 0 to 0.5 for sodium, 0 to 1.5 for boron, 0 to 2 for titanium, 0 to 1 for lead, 0 to 2 for zirconium, and 0 to 1.5 for yttrium. The above MO X In the case of x=0, it is metallic and not transparent, and in the range of x, The upper limit is the value when completely oxidized. In the present invention, silicon oxide and aluminum oxide are preferably used, and silicon oxide having an x ​​value in the range of 1.0 to 2.0 and aluminum oxide having an x ​​value in the range of 0.5 to 1.5 can be used. The oxygen barrier layer may be formed of one of these barrier materials, or may be a combination of two or more of them, or may be a mixture of two or more of them. It may be composed of one layer or multiple layers of the same or different compositions, and in the case of multiple layers, they do not have to be laminated adjacently.

[0017] As the resin film supporting the above-mentioned inorganic vapor deposition layer, a resin film that has excellent mechanical, physical, chemical and other properties, and is particularly strong and tough, and has heat resistance, can be used since the inorganic vapor deposition layer is provided on it.

[0018] Specifically, in the present invention, examples of the resin film supporting the inorganic vapor deposition layer include polyester-based resin films such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT), polyamide-based resin films such as various nylons, polyethylene-based resins, polypropylene-based resins, cyclic polyolefin resins, polystyrene-based resins, acrylonitrile-styrene copolymers (AS resins), acrylonitrile-butadiene-styrene copolymers (ABS resins), polyolefin films such as polybutene resin films, polyvinyl chloride-based resins, polycarbonate-based resins, polyimide-based resins, polyamideimide-based resins, polyarylphthalate resins, silicone-based resins, polysulfone-based resins, polyphenylene sulfide-based resins, polyethersulfone-based resins, polyurethane-based resins, cellulose-based resins, poly(meth)acrylic resins, polyvinylidene chloride films, acetal-based resin films, fluorine-based resins, and others. In the present invention, it is preferable to use a resin film made of biaxially oriented polyethylene terephthalate, polyacrylonitrile, ethylene-vinyl alcohol copolymer, non-oriented polypropylene (CPP), low-density polyethylene, linear low-density polyethylene, or the like, which can be heat-sealed or bonded with an adhesive. The resin film used in the vapor-deposited resin film may be a resin film constituting a base layer.

[0019] As a method for forming an inorganic vapor deposition layer, the inorganic vapor deposition layer can be formed on a resin film using, for example, a physical vapor deposition method (Physical Vapor Deposition method, PVD method) such as a vacuum deposition method, a sputtering method, an ion plating method, a cluster ion beam method, or a chemical vapor deposition method (Chemical Vapor Deposition method, CVD method) such as a plasma chemical vapor deposition method, a thermal chemical vapor deposition method, a photochemical vapor deposition method, or the like, using the inorganic compounds as raw materials.

[0020] More specifically, in the above-mentioned PVD method, for example, a take-up type deposition machine is used, and a resin film coming off a winding roll in a vacuum chamber is placed into a deposition chamber, where a deposition source heated in a crucible is evaporated, and if necessary, an inorganic deposition layer is formed on the resin film on a cooled coating drum through a mask while oxygen or the like is sprayed from an oxygen outlet, and then the resin film with the inorganic deposition layer formed thereon is wound up onto a take-up roll, thereby producing a resin film with an inorganic deposition layer according to the present invention.

[0021] Meanwhile, in the above-mentioned CVD method, a mixed gas of, for example, an organic silicon compound as a monomer gas, oxygen gas, an inert gas, etc., supplied from a vapor deposition raw material volatilization and supply device in the vapor deposition chamber, is introduced onto the surface of a resin film unwound from a winding roll arranged in a vapor deposition chamber, on the peripheral surface of a cooling electrode drum, and a resin film on which a vapor deposition layer of silicon oxide is formed by plasma can be produced.

[0022] In the above, the thickness of the inorganic vapor deposition layer is preferably 30 Å to 3000 Å, more preferably 40 Å to 2500 Å, and even more preferably 50 Å to 2000 Å, in order to obtain sufficient oxygen barrier properties. More specifically, in the above PVD method, the thickness of the inorganic vapor deposition layer made of aluminum oxide is preferably 30 Å to 1000 Å, and more preferably about 50 Å to 500 Å. In the above CVD method, the thickness of the inorganic deposition layer made of silicon oxide is 30 Å to 3 000 Å is preferable, and 100 Å to 300 Å is more preferable. In the above, in the case of an inorganic vapor deposition layer made of a metal oxide or an inorganic substance, if the thickness of the inorganic vapor deposition layer exceeds the above range, cracks or the like are likely to occur in the inorganic vapor deposition layer, which may result in a decrease in barrier properties and may also lead to problems such as an increase in material costs, which is undesirable. Also, if the thickness is less than the above range, it is undesirable because it may be difficult to achieve oxygen barrier properties.

[0023] An oxygen barrier resin coating film or an oxygen barrier resin film made of an oxygen barrier resin can also be used as an oxygen barrier material, and can simultaneously exhibit gas barrier properties against water vapor and the like, aroma retention, and the like. Examples of oxygen barrier resins that can be used include films or coatings of resins with excellent gas barrier properties, such as polyvinylidene chloride resins (PVDC), polyester resins, polyamide resins (particularly aromatic polyamides such as nylon MXD6), ethylene-vinyl alcohol copolymers (EVOH) with an ethylene content of 25 mol % to 50 mol % obtained by fully saponifying an ethylene-vinyl acetate copolymer (vinyl acetate is approximately 79 wt % to 92 wt %), polyvinyl alcohol, polyacrylonitrile, and others. The thickness of the oxygen barrier resin coating film or the oxygen barrier resin film is not limited, but is preferably 0.5 μm to 300 μm, and more preferably 1 μm to 100 μm. The resin film with an inorganic deposition layer preferably has a water vapor permeability of 3.0 g / m2 or less, as measured in accordance with JIS K7129 at a temperature of 40° C. and a humidity of 100% RH. 2 · day or less, and more preferably 2.0 g / m 2 days or less, and more preferably is 1.5g / m 2 If the water vapor transmission rate is within the above range, the package This makes it possible to sufficiently prevent water vapor from entering the content storage section inside the package from the outside. The resin film with an inorganic vapor deposition layer preferably has an acid permeability of 1.0 cc / m2 or less, as measured in accordance with JIS K7126 under an environment of 23°C temperature and 90% RH. 2 a tm·day or less, more preferably 0.5cc / m 2 ·atm·day or less , and more preferably 0.1 cc / m 2 ·atm·day or less. The oxygen permeability is the above number. If the value range is satisfied, the intrusion of oxygen from the outside of the package into the content-accommodating portion inside the package can be sufficiently suppressed.

[0024] When forming the inorganic deposition layer, SiO x Pretreatment such as plasma reduces the resin to be vapor-deposited. By cleaning the surface of the film and generating polar groups or free radicals on the surface, it is possible to increase the tight adhesion between the inorganic vapor deposition layer and the resin film. Furthermore, when two or more inorganic vapor deposition layers are continuously laminated using a plasma enhanced chemical vapor deposition apparatus consisting of at least two deposition chambers, each layer can be deposited so as to have high gas barrier properties, thereby obtaining gas barrier properties that are even higher than those of a single layer. Furthermore, by continuously depositing the layers without exposing them to the atmosphere, it is possible to prevent foreign matter, dust, etc., which may cause cracks, from being mixed between the inorganic vapor deposition layers, and the gas barrier properties are improved. Furthermore, if the compositions of the respective vapor-deposited layers are different, the inorganic vapor-deposited layers are different discontinuous layers, so that the permeation of oxygen gas, water vapor, etc. can be more efficiently suppressed.

[0025] When the oxygen barrier layer is formed of a resin film with an inorganic vapor deposition layer, the layer can be laminated by bonding the inorganic vapor deposition layer surface to the base layer via an adhesive resin layer so as to face the base layer. When laminating a resin film with an inorganic vapor deposition layer, if necessary, in order to strengthen the adhesive strength with other layers, the surface of the resin film with an inorganic vapor deposition layer may be subjected in advance to a physical surface treatment such as corona discharge treatment, ozone treatment, plasma treatment, glow discharge treatment, sandblasting treatment, etc., or a chemical surface treatment such as oxidation treatment using chemicals, to form a surface treatment layer.

[0026] <Oxygen-absorbing adhesive layer> The oxygen-absorbing adhesive layer is a layer formed using an oxygen-absorbing adhesive composition.

[0027] Oxygen-absorbing adhesive composition The oxygen-absorbing adhesive composition of the present invention is an oxygen-absorbing adhesive composition that contains at least an oxygen-absorbing compound and an oxidation-promoting catalyst. The oxygen-absorbing adhesive composition may further contain a modifier, a diluting solvent, various additives, and the like, as necessary.

[0028] The oxygen-absorbing adhesive composition may be prepared by adding an oxygen-absorbing compound to an existing adhesive composition, or the oxygen-absorbing adhesive composition may be prepared using an oxygen-absorbing compound as a resin component. Here, the existing oxygen-absorbing adhesive composition may be a one-liquid oxygen-absorbing adhesive composition or a two-liquid oxygen-absorbing adhesive composition. The oxygen absorbing adhesive composition can contain one or more oxygen absorbing compounds. The oxygen-absorbing adhesive composition and / or the above-mentioned existing adhesive composition may be curable or non-curable. If it is curable, it may be any of heat curable, photocurable, electron beam curable, etc. The oxygen absorbing compound may or may not react with components contained in existing adhesive compositions, or may react with other oxygen absorbing compounds. Depending on the presence or absence of the above reaction and the type of reaction, one or more oxygen absorbing compounds can be selected and used from among those having no functional group, those having a (co)polymerizable functional group, and those having a functional group capable of reacting as a base agent or a curing agent.

[0029] Specifically, for example, an oxygen absorbing compound without a functional group and / or an oxygen absorbing compound with a functional group can be added to a two-liquid urethane adhesive composition containing an isocyanate compound and a hydroxyl group-containing compound. In this case, the functional group is preferably an isocyanate group and / or a hydroxyl group. For example, the oxygen-absorbing adhesive composition can be prepared by combining the main component and curing agent with an isocyanate compound and an oxygen-absorbing compound having a hydroxyl group, with a hydroxyl group-containing compound and an oxygen-absorbing compound having an isocyanate group, or with an oxygen-absorbing compound having a hydroxyl group and an oxygen-absorbing compound having an isocyanate group. The oxygen absorbing adhesive composition is preferably a urethane-based oxygen absorbing adhesive composition.

[0030] The solid content in the oxygen-absorbing adhesive composition is not particularly limited, but is preferably 20% by mass or more and 100% by mass or less.

[0031] The content of the oxygen absorbing compound in the solid content excluding the oxidation-promoting catalyst in the oxygen absorbing adhesive composition is preferably 40% by mass or more and 100% by mass or less. If it is less than the above range, there is a risk that the oxygen absorption will be insufficient. When it is 100% by mass, it means that the oxygen absorbing compound can be used as a resin component of the adhesive composition, and it has sufficient adhesiveness by itself, has a functional group that can be cured by itself, or is used by mixing an oxygen absorbing compound having a functional group as a main agent and an oxygen absorbing compound having a functional group as a curing agent.

[0032] The content of the oxidation-promoting catalyst in the oxygen-absorbing adhesive composition is preferably 10 ppm or more and 6000 ppm or less relative to the oxygen-absorbing compound. If the content is less than the above range, the oxygen absorption may be insufficient. If the amount is more than this range, the oxygen absorption properties are likely to become unstable, and the oxygen absorption properties may be consumed before the package is produced, which may impair the effect of inhibiting deterioration of the package contents due to oxygen after the package is produced.

[0033] [Oxygen absorbing compound] The oxygen-absorbing compound of the present invention has oxygen-absorbing properties, generates little odor, and can be used alone or as a mixture with a resin or a resin composition. The oxygen-absorbing compound of the present invention is an unsaturated five-membered ring-containing compound having one or more unsaturated five-membered rings, in which any bond between five carbon atoms constituting the unsaturated five-membered ring is a carbon-carbon double bond, and a monovalent and / or divalent or higher electron-donating organic group 1 is bonded to the unsaturated five-membered ring. When there is one unsaturated five-membered ring, the five-membered ring or the organic group 1 has a functional group having active hydrogen, or a group in which the active hydrogen of the functional group having active hydrogen is substituted with a monovalent organic group 2, and when there are two or more unsaturated five-membered rings, the unsaturated five-membered rings are bonded to each other via a divalent or higher organic group 2 that substitutes the active hydrogen of the active hydrogen group on each of the organic groups 1. When there are two or more such unsaturated five-membered rings in one molecule, the unsaturated five-membered rings are bonded to each other via a structure in which an active hydrogen of a functional group having an active hydrogen on each of the five-membered rings or organic group 1 is substituted with a divalent or higher organic group 2. The unsaturated five-membered ring, organic group 1, and organic group 2 present in one molecule may each be one or two or more kinds, and the number may be one or two or more. The organic group 1 bonded to one unsaturated five-membered ring may be one or two or more. Furthermore, the oxygen-absorbing compound may be a mixture of molecules having two or more structures in which the types and numbers of the unsaturated five-membered ring, organic group 1, and organic group 2 present in one molecule are different, as described above.

[0034] Organic group 1 donates electrons to the unsaturated five-membered ring, thereby increasing the electron density of the carbon-carbon double bond portion of the unsaturated five-membered ring, thereby increasing the reactivity with oxygen and improving the oxygen absorbency. It is preferable that no electron-withdrawing group is bonded to the unsaturated five-membered ring, since the electron-withdrawing group is bonded to the unsaturated five-membered ring, the electron density of the carbon-carbon double bond portion of the unsaturated five-membered ring is lowered, the reactivity with oxygen is reduced, and the oxygen absorption is reduced. Specific molecular structures of the oxygen-absorbing compound include, for example, one unsaturated five-membered ring bonded to a monovalent or divalent organic group 1, one unsaturated five-membered ring bonded to a monovalent or divalent organic group 1 and a monovalent organic group 2 in that order, two unsaturated five-membered rings bonded via a divalent organic group 1 and a divalent organic group 2, and three unsaturated five-membered rings bonded via a divalent organic group 1 and a trivalent organic group 2.

[0035] In addition, the oxygen absorbing compound does not have to have a crosslinkable functional group, but can have one. The crosslinkable functional group may be a functional group that was possessed by the compound from which the organic group 2 is derived, or may be a functional group that has been added by chemical modification. Because the oxygen-absorbing compound has a crosslinkable functional group, when the oxygen-absorbing compound is mixed with a resin or a resin composition, the oxygen-absorbing compound has increased compatibility with the resin or the resin composition or becomes part of the crosslinked structure of the resin or the resin composition, making it less likely to bleed from the resin or the resin composition, or from the cured product of the resin composition, and the content of the oxygen-absorbing compound in the resin or the resin composition can be increased. Specific examples of the crosslinkable functional group include an aliphatic hydroxyl group, an aromatic hydroxyl group, an isocyanate group, an amino group, an epoxy group, a (meth)acrylic group, etc. Among these, an isocyanate group and an aliphatic hydroxyl group are preferred. In the case where the oxygen absorbing compound has a crosslinkable functional group, the number of the crosslinkable functional groups contained in one molecule is preferably 1 or 2 or more. It may be one or more kinds. The functional group equivalent of the crosslinkable functional group is not particularly limited, but is preferably 500 to 20,000, more preferably 1,000 to 15,000, and even more preferably 1,500 to 10,000.

[0036] The number average molecular weight of the oxygen absorbing compound is preferably 100 to 10,000, more preferably 200 to 5,000, and even more preferably 300 to 2,500. If the number average molecular weight is smaller than the above range, it is likely to precipitate when mixed with a resin or a resin composition. If the number average molecular weight is larger than the above range, it is likely to require a large amount of dilution solvent to be contained when mixed with a resin or a resin composition because the viscosity of the mixture increases, making it difficult to obtain a thick film or layer, and coating suitability is likely to deteriorate.

[0037] The oxygen absorbing action of the oxygen absorbing compound of the present invention can be promoted by heating or adding a catalyst.

[0038] (unsaturated five-membered ring) The unsaturated five-membered ring of the oxygen-absorbing compound has a carbon-carbon double bond therein. Here, the carbon-carbon double bond is any bond between the five carbon atoms constituting the unsaturated five-membered ring, and there may be one or two carbon-carbon double bonds in one unsaturated five-membered ring. The carbon-carbon double bond reacts with oxygen molecules in the air and captures the oxygen molecules, thereby causing the oxygen absorbing compound to exhibit its oxygen absorbing properties. Examples of compounds from which the above-mentioned unsaturated five-membered ring or the unsaturated five-membered ring to which the electron-donating organic group 1 is bonded include cyclopentadiene, dicyclopentadiene, norbornene, and derivatives thereof. The oxygen-absorbing compound can have an unsaturated five-membered ring derived from one or more of these selected from the group consisting of these. The concentration of the unsaturated five-membered ring in the oxygen-absorbing compound is not particularly limited, but is preferably 1% by mass or more and 70% by mass or less, and more preferably 5% by mass or more and 60% by mass or less. If the concentration is lower than the above range, the oxygen absorption is likely to be insufficient, and it is difficult to obtain an oxygen-absorbing compound with a higher absorption capacity than the above range, and the balance between various physical properties is likely to be poor.

[0039] (Electron-donating organic group 1) Specific examples of the organic group 1 include an alkyl group, an alkylene group, a cyclic alkylene group, etc. Among these, a cyclic alkylene group is preferable, and one which constitutes an aliphatic bicyclic alkylene group together with the unsaturated five-membered ring is more preferable. Specific examples of the cyclic alkylene group include a cyclopropylene group, a cyclobutylene group, a cyclopentylene group, a cyclohexylene group, a cycloheptylene group, a cyclooctylene group, etc. Among these, a cyclopentylene group is more preferable.

[0040] (Electron-withdrawing organic group) Specific examples of the electron-withdrawing group include a phenyl group, a phenylene group, a carbonyl group, and a halogen. Indenes and coumarones in which only these electron-withdrawing groups are bonded to an unsaturated five-membered ring have a low electron density in the carbon-carbon double bond portion of the unsaturated five-membered ring, which reduces the reactivity with oxygen and results in low oxygen absorption.

[0041] (Functional group having active hydrogen) A functional group having an active hydrogen is chemically reactive. Specific examples of the functional group having an active hydrogen include a primary amino group, a secondary amino group, an aliphatic hydroxyl group, an aromatic hydroxyl group, an imino group, a carboxyl group, a urethane group, and a urea group. Among these, a primary amino group, a secondary amino group, an aliphatic hydroxyl group, and an aromatic hydroxyl group are preferred, and an aliphatic hydroxyl group is more preferred.

[0042] (organic group 2) Organic group 2 is a monovalent and / or divalent or higher group that substitutes an active hydrogen of a functional group having an active hydrogen on the five-membered ring or organic group 1 and is bonded to the five-membered ring or organic group 1. When there are two or more such unsaturated five-membered rings in one molecule, the unsaturated five-membered rings are bonded to each other via a structure in which the active hydrogen of a functional group having an active hydrogen is substituted with a divalent or higher organic group 2. As a specific example, a functional group having an active hydrogen on organic group 1 reacts with an isocyanate group of an isocyanate compound having a structural portion from which organic group 2 is derived, and the active hydrogen is substituted for organic group 2, resulting in bonding via a urethane group. By bonding the organic group 2, the oxygen absorbing compound can have two or more of the unsaturated five-membered rings in one molecule, and furthermore, when mixed with a resin or a resin composition to prepare a mixture, the compatibility, dispersibility, and reactivity can be improved.Furthermore, the mixture or the cured product of the mixture can be adjusted to be soft.

[0043] The organic group 2 may be an aliphatic group, an aromatic group, or may have both an aliphatic group and an aromatic group. The organic group 2 present in one molecule of the oxygen-absorbing compound may be of one type or of two or more types. The organic group 2 is preferably a group containing a structural portion derived from an isocyanate compound and / or a hydroxyl group-containing compound. Here, the structural portion derived from an isocyanate compound and / or a hydroxyl group-containing compound includes a structural portion derived from a reaction product of an isocyanate compound and a hydroxyl group-containing compound.

[0044] (Isocyanate compounds) Examples of isocyanate compounds from which the organic group 2 is derived include tetramethylene diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, isophorone diisocyanate, norbornane diisocyanate, xylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, phenylene diisocyanate, diphenylether diisocyanate, hydrogenated diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate, and their trimethylolpropane adducts, biuret bodies, allophanate bodies, isocyanurate bodies (trimers), and various derivatives thereof. Among these, biuret bodies of toluene diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate are preferred. In the present invention, one or more types selected from the group consisting of these isocyanate compounds can be used as the origin of the structural portion of the monovalent and / or divalent or higher hydrocarbon group. When two or more types are used, two types may be used in the same molecule of the oxygen-absorbing compound, or molecules of the oxygen-absorbing compound having different types may be mixed.

[0045] The number average molecular weight of the isocyanate compound is preferably 100 to 10,000, more preferably 160 to 5,000. If the number average molecular weight is smaller than the above range, it is likely to precipitate when mixed with a resin or a resin composition. If the number average molecular weight is larger than the above range, it is likely to require a large amount of dilution solvent to be contained when mixed with a resin or a resin composition because the viscosity of the mixture increases, making it difficult to obtain a thick film or layer, and coating suitability is likely to deteriorate.

[0046] (Hydroxy group-containing compound) The hydroxyl group-containing compound is a compound from which the above organic group 2 is derived, and has two or more hydroxyl groups. Examples of the hydroxyl group-containing compound include polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof. Among these, polyether polyols and polyolefin polyols are preferred. In order to prevent odor generation, the hydroxyl group-containing compound is preferably one that does not have a double bond in the aliphatic chain of the main skeleton or one that has two hydroxyl groups. Compounds that have a hydroxyl group at the end are preferred because they are more readily available, but they do not have to be at the end. In the present invention, one or more types selected from the group consisting of these can be used as the hydroxyl group-containing compound from which the organic group 2 is derived. When two or more types are used, two types may be used in the same molecule of the oxygen-absorbing compound, or molecules of the oxygen-absorbing compound having different types may be mixed. The number average molecular weight of the hydroxyl group-containing compound is preferably 500 to 10,000, more preferably 750 to 5,000, and even more preferably 1,000 to 3,000. If the number average molecular weight is smaller than the above range, it is likely to precipitate when mixed with a resin or a resin composition. If the number average molecular weight is larger than the above range, it is likely to require a large amount of dilution solvent to be contained when mixed with a resin or a resin composition because the viscosity of the mixture increases, making it difficult to obtain a thick film or layer, and coating suitability is likely to deteriorate.

[0047] Polyhydric alcohols Polyhydric alcohols are monomers having two or more hydroxyl groups. Specific examples of polyhydric alcohols include diols such as ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,3-butanediol, 1,6-hexanediol, cyclohexanedimethanol, 1,8-octanediol, 1,9-nonanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2-methyl-1,3-propanediol, 2,2,4-trimethyl-1,3-pentanediol, 2,4-diethyl-1,5-pentanediol, 1,12-octadecanediol, and 2,2'-oxydiethanol, as well as glycerin, mannitol, and sorbitol. Among the above, ethylene glycol is preferred in terms of oxygen absorption.

[0048] Polyolefin polyol The polyolefin polyol is a polyolefin resin having two or more hydroxyl groups. Specific examples of polyolefin polyols include those whose main skeleton is a polyolefin such as polyethylene, polypropylene, polybutylene, polybutadiene, hydrogenated polybutadiene, polyisoprene, hydrogenated polyisoprene, ethylene-vinyl acetate copolymer, ethylene-ethyl (meth)acrylate copolymer, ethylene-(meth)acrylic acid copolymer, and ethylene-propylene copolymer, and which have a hydroxyl group. Among these, those having an ethylene-vinyl acetate copolymer or hydrogenated polyisoprene as the main skeleton are particularly preferred.

[0049] Polyether polyol Polyether polyol is a polyether resin having two or more hydroxyl groups. Polyether polyols are obtained, for example, by dehydration condensation of the above-mentioned polyhydric alcohols or polyolefin polyols, and have a polyether structure in the main skeleton and a hydroxyl group. Specific examples of polyether polyols include diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene ether diol, polypropylene ether diol, polybutylene ether diol, glycerin-modified polyether polyols, etc. Among these, polypropylene ether diol is particularly preferred.

[0050] Polyester polyol The polyester polyol is a polyester resin having two or more hydroxyl groups. The polyester polyols are obtained, for example, by esterification reaction between various polyvalent carboxylic acids or derivatives thereof and the above-mentioned polyhydric alcohols, polyolefin polyols, polyether polyols, etc., and have a polyester structure in the main skeleton and hydroxyl groups. Specific examples of polycarboxylic acids include adipic acid, phthalic acid, isophthalic acid, terephthalic acid, maleic acid, fumaric acid, succinic acid, oxalic acid, malonic acid, pimelic acid, azelaic acid, sebacic acid, suberic acid, glutaric acid, 1,4-cyclohexanedicarboxylic acid, and trimellitic acid. Derivatives of these polycarboxylic acids include esters, acid anhydrides, and acylation products. Among the above, polyester polyols using two or more kinds of polyhydric alcohols and two or more kinds of polyvalent carboxylic acids in combination are preferred in order to reduce crystallinity.

[0051] Polycarbonate polyol Polycarbonate polyol is a polycarbonate resin having two or more hydroxyl groups. Polycarbonate has a polyol-derived portion in the main skeleton, and this polyol-derived portion may be derived from the above-mentioned polyhydric alcohols, polyolefin polyol, polyether polyol, polyester polyol, or the like. Among these, polycarbonate polyols using two or more kinds of polyhydric alcohols in combination are preferred in order to reduce crystallinity.

[0052] Poly(meth)acrylic acid ester polyol The poly(meth)acrylate polyol is a (meth)acrylate (co)polymer having two or more hydroxyl groups. Poly(meth)acrylic acid ester polyol can be obtained, for example, by using a hydroxyl group-containing monomer such as 2-hydroxyethyl methacrylate or a (meth)acrylic acid ester having a hydroxyl group synthesized from one (meth)acrylic acid or a derivative thereof and one diol, and polymerizing the hydroxyl group-containing monomer with itself or copolymerizing it with a (meth)acrylic acid ester not having a hydroxyl group. As the diol used in synthesizing the (meth)acrylic ester having a hydroxyl group, the above-mentioned diols, polyolefin polyol, polyether polyol, etc. can be used. Among these, a poly(meth)acrylic acid ester copolymer using 2-hydroxyethyl methacrylate is preferred.

[0053] Phenoxy resin Phenoxy resin is a resin obtained by reacting a polyhydric phenol compound with a polyhydric epoxy compound, and has a structure in which an aliphatic hydroxyl group is generated at the bond formed by reaction between an aromatic hydroxyl group and an epoxy group. As the phenoxy resin, those obtained by reacting a bisphenol with a diglycidyl etherified bisphenol are readily available and are common. Examples of the polyhydric phenol compound include bisphenol A and bisphenol F, and examples of the polyfunctional epoxy compound include bisphenol A diglycidyl ether and bisphenol F diglycidyl ether. Among these, phenoxy resins using bisphenol A are preferred. The terminal of the phenoxy resin may be an aromatic hydroxyl group or an epoxy group.

[0054] · Urethane chain-extended polyol The urethane chain-extended polyol is a compound obtained by extending the hydroxyl group-containing compound with a urethane chain. It is a polyol having two or more hydroxyl groups obtained by the above process. The urethane chain-extended polyol can be obtained, for example, by polymerizing the above-mentioned various hydroxyl group-containing compounds with the above-mentioned isocyanate-based compounds to extend the urethane chain. If necessary, diamines or amino alcohols may be used in combination for polymerization. Among the above, urethane chain-extended polyols obtained by reacting the above-mentioned various hydroxyl group-containing compounds having hydroxyl groups at both ends with a diisocyanate compound are preferred.

[0055] (Specific examples of oxygen absorbing compounds) Specific examples of the oxygen-absorbing compound are given below. 3a,4,5,6,7,7a-Hexahydro-4,7-methano-1H-indenol represented by formula (1), 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-indenamine represented by formula (1-b), and 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-inden-1-ol represented by formula (1-c) are examples of oxygen absorbing compounds each having one unsaturated five-membered ring and one organic group 1, and the organic group 1 has a hydroxyl group or an amino group as a functional group having active hydrogen. [ka] [ka] [ka]

[0056] The oxygen absorbing compound represented by formula (2) is, for example, a compound having a hydroxyl group, which is a functional group having an active hydrogen on organic group 1 of the oxygen absorbing compound represented by formula (1), and an isocyanate compound R 1 (NCO) a The isocyanate group of the hydroxyl group reacts with the The active hydrogen is replaced, and a number of the unsaturated five-membered rings and the organic group 1 are R 1 It can be obtained by combining through It is an oxygen absorbing compound that can [ka] (wherein a is a number equal to or greater than 1, and R 1 is a group with one or more carbon atoms. The organic group may include at least an alkylene and / or phenylene structure, and may further include a structure derived from one or more members selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.

[0057] The oxygen absorbing compound represented by formula (5) is a compound represented by formula (2) in which a=2 and R 1 For example, the isocyanate compound OCN-R 4 -NCO and hydroxyl group-containing compounds HO-R 5 Oxygen absorption when the group is derived from -OH and contains a structural part generated by the reaction of the two It is a volatile compound. [ka] (In the formula, f is a number equal to or greater than 0, and R 4 and R 5Each of the above is an organic group having one or more carbon atoms, containing at least an alkylene and / or phenylene structure, and further may contain a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.

[0058] The oxygen-absorbing compound represented by formula (3) may be, for example, 1 Isocyanate The oxygen-absorbing compound is derived from a nate compound and a hydroxyl group-containing compound, contains a structural portion formed by the reaction of the two, and contains hydroxyl groups as a result of residual excess hydroxyl groups or chemical modification. [ka] (wherein b and c are each a number equal to or greater than 1, and R 2 is the number of carbon atoms It is one or more organic groups, and contains at least an alkylene and / or phenylene structure, and further contains a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.

[0059] The oxygen-absorbing compound represented by formula (4) may be, for example, 1 Isocyanate The oxygen-absorbing compound is derived from a hydroxyl group-containing compound and a carboxylate-based compound, contains a structural part formed by the reaction of the two, and contains an isocyanate group due to residual excess isocyanate groups or chemical modification. [ka] (wherein, d and e are each a number equal to or greater than 1; R 3 is the number of carbon atoms It is one or more organic groups, and contains at least an alkylene and / or phenylene structure, and further contains a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.

[0060] [Oxidation promotion catalyst] The oxidation-promoting catalyst is a compound that promotes the action of the oxygen-absorbing compound absorbing oxygen molecules and being oxidized. Examples of the oxidation-promoting catalyst include peroxides and compounds containing cations made of transition metals. Specific examples of the peroxide include hydrogen peroxide. The compound containing a cation made of a transition metal is preferably a metal soap made of a transition metal-containing compound capable of releasing a cation or complex of a transition metal atom and an anion or ligand made of a fatty acid. As the transition metal, cobalt, manganese, iron, nickel, copper, etc. are preferred, and as the anion or ligand, anion or ligand formed of stearic acid, naphthenic acid, octylic acid, acetylacetonate, etc. are preferred. The oxidation-promoting catalyst may be a metal soap formed by combining a cation made of one or more transition metals selected from the group consisting of the above transition metals with an anion made of one or more fatty acids selected from the group consisting of the above long-chain fatty acids. Specific compounds include cobalt octylate, cobalt acetylacetone (II), cobalt acetylacetone (III), manganese acetylacetone (III), and iron acetylacetone (III).

[0061] [Denaturant] The modifier is a compound having a functional group that reacts with the oxygen absorbing compound when the oxygen absorbing compound has a functional group, and various reactive monomers and resins can be used. By including a modifier in the oxygen-absorbing adhesive composition, it is possible to bond the oxygen-absorbing compound to other components in the oxygen-absorbing adhesive composition, to adjust the content of the oxygen-absorbing compound in the oxygen-absorbing adhesive composition, and to adjust the hardness of the cured product of the oxygen-absorbing adhesive composition.

[0062] For example, when the oxygen absorbing compound has a hydroxyl group or an isocyanate group, a modifying agent made of an isocyanate compound and / or a hydroxyl group-containing compound can be used. When the oxygen-absorbing adhesive composition is a urethane-based one, the equivalent ratio NCO / OH of the oxygen-absorbing adhesive composition is preferably 0.5 or more and 8 or less. If it is less than the above range, the curing of the oxygen-absorbing adhesive composition may be insufficient, and sufficient lamination strength (adhesive strength) may not be obtained, whereas if it is greater than the above range, the pot life of the oxygen-absorbing adhesive composition may be too short.

[0063] (Isocyanate compounds for use as modifiers) The isocyanate compound for the modifier can be the isocyanate compound used in the synthesis of the oxygen absorbing compound, and any of aromatic isocyanates, aliphatic isocyanates, and urethane chain-extended isocyanates thereof can be used. In addition, in order for the oxygen absorbing adhesive composition to harden, it is preferable to use one having two or more isocyanate groups in one molecule. However, it is also possible to use an isocyanate compound having one isocyanate group in one molecule in the range that does not inhibit the sufficient effect of the oxygen absorbing adhesive composition. As the isocyanate compound having two or more isocyanate groups in one molecule, a biuret form of hexamethylene diisocyanate is particularly preferred.

[0064] Specific examples of isocyanate compounds include tetramethylene diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, isophorone diisocyanate, norbornane diisocyanate, xylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, phenylene diisocyanate, diphenylether diisocyanate, polymethylene polyphenyl polyisocyanate, and their trimethylolpropane adducts, biuret compounds, allophanate compounds, isocyanurate compounds (trimers), and various derivatives thereof. Among these, the biuret compounds of toluene diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate are preferred.

[0065] (Hydroxyl-containing compounds for use as modifiers) The hydroxyl group-containing compound for the modifier can be the hydroxyl group-containing compound used in the synthesis of the oxygen absorbing compound, and can be any of aromatic hydroxyl group-containing compounds, aliphatic hydroxyl group-containing compounds, and urethane chain-extended polyols thereof. In addition, in order for the oxygen absorbing adhesive composition to harden, it is preferable to have two or more hydroxyl groups in one molecule. However, it is also possible to use a hydroxyl group-containing compound having one hydroxyl group in one molecule in the range that does not inhibit the sufficient effect of the oxygen absorbing adhesive composition. As the hydroxyl group-containing compound having two or more hydroxyl groups in one molecule, either an aromatic hydroxyl group-containing compound or an aliphatic hydroxyl group-containing compound can be used, and either an alcohol-based or a phenol-based compound can be used. As the isocyanate compound having two or more isocyanate groups in one molecule, polyalkylene ether diols and urethane chain extended polyols of polyalkylene ether diols are particularly preferred.

[0066] [Dilution solvent] The dilution solvent is not particularly limited as long as it uniformly dissolves or disperses the oxygen-absorbing compound and the oxidation-promoting catalyst, makes the oxygen-absorbing adhesive composition uniform, and is compatible with the dry lamination process. For example, an ester-based dilution solvent, a ketone-based dilution solvent, a hydrocarbon-based dilution solvent, etc. can be used. Specific examples of the ester-based diluent solvent include ethyl acetate, butyl acetate, etc., specific examples of the ketone-based diluent solvent include methyl ethyl ketone, etc., and specific examples of the hydrocarbon-based diluent solvent include toluene, etc. Among these, ethyl acetate is easy to use and is preferable.

[0067] [Various additives] The oxygen-absorbing adhesive composition may contain various additives as necessary. For example, curing accelerators, curing regulators for extending the pot life, antioxidants for suppressing a decrease in oxygen absorption during storage or use of the oxygen absorbing adhesive composition and before the contents are placed in a package, adhesive assistants, tackifiers, leveling agents, ultraviolet absorbers, defoamers, colorants, etc. Pigments and extender pigments can also be added.

[0068] (Cure accelerator) There are no particular limitations on the curing accelerator that can be used as long as it accelerates the curing reaction of the oxygen-absorbing adhesive composition. Specific examples of the curing accelerator include metal-containing compounds such as dibutyltin dilaurate, dibutyltin diacetate, dioctyltin dilaurate, dibutyltin dimaleate, tetrabutyl titanate, and tetraisopropyl titanate, and tertiary amines such as 1,8-diaza-bicyclo(5,4,0)undecene-7, 1,5-diazabicyclo(4,3,0)nonene-5, and triethanolamine. One or more types selected from the group consisting of these can be used.

[0069] (hardening regulator) When the pot life of the oxygen-absorbing adhesive composition is shortened due to the oxidation-promoting catalyst contained therein, the pot life can be extended by using a cure regulator in combination. Specific examples of the hardening regulator include phosphoric acids, such as orthophosphoric acid, metaphosphoric acid, polyphosphoric acid, and ester derivatives thereof. One or more selected from the group consisting of these can be used. The amount of reaction regulator added is preferably 200 ppm or more and 400 ppm or less based on the resin component of the oxygen-absorbing adhesive composition. If the amount is less than this range, it is difficult to obtain the effect of extending the pot life, and if the amount is more than this range, there is a risk that the curing of the oxygen-absorbing adhesive composition is inhibited.

[0070] (Antioxidants) The oxygen-absorbing adhesive composition may contain an antioxidant in order to suppress deterioration of oxygen absorption properties during storage or use of the oxygen-absorbing adhesive composition, and even in processes before a package made using the oxygen-absorbing adhesive composition contains contents, and to maintain high oxygen absorption properties after the contents are contained. Specific examples of the antioxidant include phenols, lactones, thioethers, gallic acids, ascorbic acid, erythorbic acid, catechin, dibutylhydroxytoluene, tocopherol, citric acid, butylhydroxyanisole, phosphite, hindered amines, and aromatic amines. One or more selected from the group consisting of these antioxidants can be used. In addition, when it is assumed that heat or light is used as a trigger for expressing oxygen absorbing ability, it is preferable to use an antioxidant having low heat resistance and light resistance, such as ascorbic acid or tocopherol, and it is not preferable to use an antioxidant having high heat resistance and light resistance, such as a phenol-based antioxidant. The amount of the antioxidant added is preferably 10 ppm or more and 10000 ppm or less relative to the oxygen absorbing compound. If the amount is less than the above range, the antioxidant effect is likely to be insufficient, and if the amount is more than the above range, there is a risk that the oxygen absorbing ability will decrease.

[0071] (Adhesive assistant) As an adhesion aid for aiding adhesive strength, a silane coupling agent is preferred. Examples of the silane coupling agent include γ-glycidoxypropyltrialkoxysilane, γ-methacryloxypropyltrialkoxysilane, γ-glycidoxypropylmethyldialkoxysilane, β-(3,4-epoxycyclohexyl)ethyltrialkoxysilane, γ-aminopropyltrialkoxysilane, γ-aminopropylmethyldialkoxysilane, N-(β-aminoethyl)-γ-aminopropyltrialkoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldialkoxysilane, N-butyl-3-amino-2-methylpropyltrialkoxysilane, γ-mercaptopropyltrialkoxysilane, and γ-mercaptopropylmethyldialkoxysilane. As the alkyl group, a methoxy group or an ethoxy group is preferable, and one or more groups selected from the group consisting of these can be used.

[0072] (tackifier) Examples of the tackifier include paraffin wax, polyethylene wax, rosin, rosin glycerin ester, terpene, and alkylphenol. One or more types selected from the group consisting of these can be used.

[0073] (Leveling agent) The leveling agent may be an acrylic polymer-based agent, a modified silicone-based agent, an acetylene diol-based agent, or the like. One or more types selected from the group consisting of these may be used.

[0074] (UV absorber) Examples of the ultraviolet absorbing agent include benzotriazole-based, hydroxyphenyltriazine-based, and hindered amine-based agents, and one or more types selected from the group consisting of these may be used.

[0075] (Antifoaming agent) The antifoaming agent may be a surfactant, polyether-modified silicone oil, or the like, and one or more selected from the group consisting of these may be used.

[0076] (Color pigments) Examples of color pigments include organic pigments such as anthraquinone, diketopyrrolopyrrole, perylene maroon, carbon black, dioxazine, perylene, benzimidazolone, isoindolinone, isoindoline, phthalocyanine, and indanthrene, and inorganic pigments such as yellow iron oxide, red iron oxide, azomethine copper complex, titanium oxide, and silicon oxide. One or more types selected from the group consisting of these can be used.

[0077] (Extender pigment) The extender pigment is a white or colorless pigment that is used as an extender or as an adjuster for coloring power, gloss, strength, usability, etc. Specific examples include inorganic pigments such as barium sulfate, barium carbonate, calcium carbonate, magnesium oxide, magnesium carbonate, magnesium hydroxide, barium titanate, calcium hydroxide, calcium sulfite, calcium sulfate, calcium oxide, calcium silicate, titanium oxide, silica, zeolite, and talc, and one or more types selected from the group consisting of these can be used.

[0078] <<Method for preparing oxygen-absorbing adhesive composition>> The oxygen-absorbing adhesive composition can be produced by mixing all of the components, such as the oxygen-absorbing compound, the oxidation-promoting catalyst, and, if necessary, the modifier, the diluting solvent, the various additives, etc. Alternatively, the oxygen-absorbing adhesive composition can be produced by mixing the oxygen-absorbing compound, the oxidation-promoting catalyst, and, if necessary, the modifier, the diluting solvent, the various additives, etc., with an existing adhesive composition. The method for carrying out the above mixing and the order in which the components are mixed are not particularly limited, and the method and mixing order used in preparing a general adhesive composition can be applied. Specific mixing methods include a method of dissolving in a solvent and mixing, and a method of melt-kneading. In this case, it is preferable to adjust the heating temperature in order to increase the solubility or dispersibility.

[0079] <<Method of using the oxygen-absorbing adhesive composition>> There are no particular limitations on the method of using the oxygen-absorbing adhesive composition, and any method for using it as an adhesive can be used. For example, there may be mentioned a non-solvent type lamination method in which the coating is heated to obtain an appropriate viscosity, and a dry lamination method in which a dilution solvent or other compounded adhesive is added to adjust the coating viscosity to an appropriate level. When forming an adhesive layer using the oxygen absorbing adhesive composition, the coating amount is 2 to 5 g / m 2 is preferable, and 3 to 5 g / m 2 If the amount is less than the above range, sufficient oxygen absorbency may not be obtained, whereas if the amount is more than the above range, the oxygen absorbency does not change significantly, leading to a cost disadvantage, which is undesirable.

[0080] A laminate obtained by forming and bonding an adhesive layer using the oxygen-absorbing adhesive composition is preferably aged at 20° C. or higher and 50° C. or lower for 2 days or higher and 5 days or lower. In addition, in order not to decrease the oxygen absorption property of the laminate, it is preferable to carry out the aging at a temperature as low as possible or in an inert gas atmosphere. When storing the produced laminate, it is preferable to store it at 10° C. or below or in an inert gas atmosphere in order not to decrease the oxygen absorbing property of the laminate.

[0081] About objects that can be glued There are no particular limitations on the objects to which the oxygen-absorbing adhesive composition can be adhered, and for example, it can be adhered to resin molded products, resin films, paper, metals, metal foils, inorganic vapor deposition film surfaces, and inorganic oxide vapor deposition film surfaces.

[0082] Specific examples of resins for the resin film include polyester-based resins such as polyethylene terephthalate (PET), polyamide-based resins such as various nylons, polyethylene-based resins, polypropylene-based resins, cyclic polyolefin-based resins, polystyrene-based resins, polyolefin-based resins such as acrylonitrile-styrene copolymers (AS resins), acrylonitrile-butadiene-styrene copolymers (ABS resins), and polybutene-based resins, polyvinyl chloride-based resins, polycarbonate-based resins, polyimide-based resins, polyamideimide-based resins, diallyl phthalate-based resins, silicone-based resins, polysulfone-based resins, polyphenylene sulfide-based resins, polyethersulfone-based resins, polyurethane-based resins, cellulose-based resins, poly(meth)acrylic resins, polyvinylidene chloride-based resins, acetal-based resins, and fluorine-based resins.

[0083] Specific examples of paper include strong sizing bleached or unbleached paper base materials for paper layers, or paper base materials such as pure white roll paper, kraft paper, paperboard, coated paper, processed paper, milk base paper, and the like. Specific examples of the metal foil include aluminum foil, copper foil, and stainless steel foil. A specific example of the metal of the inorganic vapor deposition layer is aluminum. Specific examples of inorganic oxides in the inorganic vapor deposition layer include silica, alumina, indium tin oxide, zinc oxide, tin oxide, titanium oxide, zirconium oxide, vanadium oxide, barium oxide, chromium oxide, silicon nitride, silicon carbide, etc. Among these, silica and alumina are preferred.

[0084] <Sealant layer> The sealant layer may be composed of a single layer, or may be composed of two or more layers having the same or different compositions. The sealant layer is a layer for heat sealing the oxygen-absorbing laminates together when forming the oxygen-absorbing paper container for liquids, and therefore preferably contains a resin having heat-sealing properties.

[0085] The sealant layer may contain any additives within the range that does not significantly impair the effects of the present invention. Examples of the additives include various resin additives that are generally used to adjust the moldability, productivity, and various physical properties of the resin film, such as antiblocking agents, slip agents, antioxidants, pigments, flow control agents, flame retardants, fillers, ultraviolet absorbers, and surfactants. The thickness of the sealant layer is preferably 25 μm or more and 150 μm or less, and more preferably 40 μm or more and 70 μm or less.

[0086] (Heat-sealable resin) Examples of resins having heat sealability include polyolefin resins, acid-modified polyolefin resins obtained by acid-modifying polyolefin resins by graft polymerization or copolymerization with unsaturated carboxylic acids or their anhydrides such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, fumaric acid, itaconic acid, etc., polyvinyl acetate resins, poly(meth)acrylic resins, polyvinyl chloride resins, and other resins. These resins can be used alone or in combination. Among the above resins, polyolefin resins are preferred because of their excellent adhesion and manufacturing costs. From the viewpoint, among the polyolefin resins, low density polyethylene, linear low density polyethylene, etc. are particularly preferable.

[0087] It is preferable to use a plant-derived polyolefin resin as a raw material for the polyolefin resin having heat sealability or the acid-modified polyolefin resin, although a fossil fuel-derived polyolefin resin may also be used. By using plant-derived polyolefin resins, the environmental impact can be reduced. The plant-derived resin can be selected with an appropriate density and MFR depending on the physical properties of the fossil fuel-derived resin used in combination and the conditions of use of the laminate. The content of the plant-derived polyolefin resin in the sealant layer is preferably 40% by mass or more and 100% by mass or less. If it is less than the above range, the effect of reducing the environmental load is reduced. When the sealant layer has a multi-layer structure, the sealant layer may have a layer containing a plant-derived polyolefin resin and a layer not containing a plant-derived polyolefin resin. For example, it is preferable that the outer surface layer that is the outermost surface of the laminate does not contain a plant-derived polyolefin resin. Furthermore, when the sealant layer has a multi-layer structure of three or more layers, it is preferable that the layers on both surfaces of the sealant layer do not contain a plant-derived polyolefin resin, and the inner layer contains a plant-derived polyolefin resin.

[0088] (Polyolefin resin) Specific examples of polyolefin resins include polyethylene, low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, ethylene-α-olefin copolymers polymerized using a metallocene catalyst, polypropylene, ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol copolymers, ionomer resins, ethylene-acrylic acid copolymers, ethylene-ethyl acrylate copolymers, ethylene-methacrylic acid copolymers, ethylene-methyl methacrylate copolymers, ethylene-propylene copolymers, methylpentene (co)polymers, butene (co)polymers, ethylene-acrylic acid copolymers, ethylene-methacrylic acid copolymers, and cyclic olefin (co)polymers such as polynorbornene. The copolymers may be random or block copolymers. Polyolefin resins are classified into, for example, polyethylene resins and polypropylene resins depending on the skeleton of the monomer used in the synthesis of the polyolefin, and may be copolymers. In the present invention, the term "polyolefin resin" is added as a general term for various types, and various types of polyolefin resins are classified into, for example, polyethylene resins and polypropylene resins. It is also referred to as polyethylene resin as a general term for ethylene. Polyolefins produced by polymerizing α-olefins such as ethylene, propene, 1-butene, 1,3-butadiene, and 1-hexene as raw materials are called polyethylene-based resins, polypropylene-based resins, polybutylene-based resins, polybutadiene-based resins, polyhexene-based resins, and the like, respectively. Common polymerization methods include, for example, a high-pressure method for low-density polyethylene, and a low-pressure polymerization method (gas phase polymerization using a Ziegler-Natta catalyst or liquid phase polymerization using a metallocene catalyst), slurry method, solution method, gas phase polymerization method, etc. for linear low-density polyethylene.

[0089] Polyolefin resins are classified into fossil fuel-derived polyolefin resins and plant-derived polyolefin resins depending on the origin of the raw material monomers. (Fossil fuel-derived polyolefin resin) In the present invention, the fossil fuel-derived polyolefin resin is a polyolefin resin that does not use a raw material monomer derived from a plant, but uses a raw material monomer obtained by pyrolysis of naphtha obtained from a fossil fuel as in the conventional method. (Plant-derived polyolefin resin) In the present invention, "plant-derived" means that it contains carbon derived from a plant raw material, for example, it means that it is produced using a compound obtained from a plant as a raw material. In a method for producing a plant-derived polyolefin resin, for example, first, sugar liquid or starch obtained from plants such as sugar cane, corn, or sweet potato is fermented by a microorganism such as yeast to produce bioethanol according to a conventional method, and this is then heated in the presence of a catalyst to obtain ethylene and α-olefins (1-butene, 1-hexene, etc.) through an intramolecular dehydration reaction or the like. Next, these are used as raw monomers for polymerization, and are polymerized in the presence of a conventional catalyst in the same manner as in the production of fossil fuel-derived polyolefin resins, to produce plant-derived polyolefin resins. The catalyst and polymerization method used in polymerization are the same as those used in the production of fossil fuel-derived polyolefin resins. As a part of the raw material monomers for polymerization or copolymerization monomers, those derived from fossil fuels can also be used in combination, if necessary.

[0090] (Method of forming sealant layer) The method for forming the sealant layer is not particularly limited, and any conventionally known method for laminating a sealant layer can be used. A sealant film consisting of one or more layers for the sealant layer may be prepared in advance, and the sealant film may be laminated by adhering it to other layers constituting the laminate via an adhesive, etc. The sealant film may be prepared by melt-extruding one or more resin compositions and forming them into a film by an inflation method, or by melt-extruding onto a roll and constricting it by an extrusion method using a T-die molding or the like to form a film. Here, it is preferable to subject one side of the prepared sealant film to a corona treatment, and then laminate the film by adhering the corona-treated side to the side to be laminated. Alternatively, the resin composition for forming the sealant layer may be melted, melt (co)extruded, and poured onto the layers to be laminated, and a sealant layer consisting of one or more layers may be laminated onto the other layers that make up the laminate by an extrusion method using a T-die molding method using a feed block method or a multi-manifold method. In either method, a multi-layer sealant film can be produced by co-melt extrusion using resin compositions of the same or different compositions.

[0091] ≪Paper base layer≫ As a material for the paper base layer, for example, a commonly known and publicly used paper base material that has excellent mechanical, physical, chemical and other properties, and in particular has supportive properties, can be used as a basic material for constituting the paper base layer of a liquid paper container. The paper base layer may be composed of one layer, or may be composed of two or more layers of the same or different composition laminated by any lamination means. The paper substrate layer may further include a resin layer. The resin layer may be formed by coating or extrusion lamination of a resin or a resin composition, or by laminating a resin film. For example, a coating resin layer having a thickness of, for example, 2 μm or more and 50 μm or less can be provided on the surface of a paper base layer to improve the water resistance of the paper base layer.

[0092] Specific examples of the resin include polyester-based resins such as polyethylene terephthalate (PET) and polyethylene naphthalate, polyolefin-based resins such as polyethylene-based resins and polypropylene-based resins, polyamide-based resins such as nylon, polyaramid-based resins, polycarbonate-based resins, polyacetal-based resins, fluorine-based resins, and other tough thermoplastic resins. When the coating resin layer is extrusion-formed, it is preferable to use a polyethylene resin, and in particular, it is preferable to use LDPE. The resin film made from the above resin may be either an unstretched film or a uniaxially or biaxially stretched film. Among the above, a biaxially oriented PET film and a biaxially oriented polypropylene film are preferably used. Furthermore, in order to improve moisture resistance and adhesion to other layers, a multilayer resin film in which polyvinylidene chloride (PVDC) is laminated onto the above-mentioned resin film by coating or the like, or a multilayer resin film laminated with polyethylene, polypropylene, cyclic olefin copolymer, fluororesin, etc. can also be used. In order to improve adhesion to adjacent layers, the surface of the resin layer may be subjected to physical surface treatments such as corona discharge treatment, ozone treatment, plasma treatment, glow discharge treatment, sandblasting treatment, etc., or chemical surface treatments such as chemical treatment using chemicals or oxidation treatment, as necessary.

[0093] (Paper base material) The paper base material can impart shapeability, flex resistance, rigidity, etc., and for example, a strong sizing bleached or unbleached paper base material for a paper layer, or a paper base material such as pure white roll paper, kraft paper, paperboard, coated paper, processed paper, milk base paper, barrier coated paper, etc. can be used. The paper base material has a basis weight of 100 g / m 2 More than 500g / m 2 Less than 120 g / m is preferable. 2 More than 400g / m 2 The following is more preferable. By setting the basis weight of the paper base material to the above numerical range, This makes it possible to improve the strength of a paper container produced using the laminate while maintaining the ease of processing of the laminate. The paper base layer may be a laminate of a plurality of layers of these papers.

[0094] In addition, in order to improve adhesion to adjacent layers, the surface of the paper substrate may be subjected to physical surface treatments such as corona discharge treatment, ozone treatment, plasma treatment, glow discharge treatment, sandblasting treatment, etc., or chemical surface treatments such as chemical treatment using chemicals or oxidation treatment, as necessary. Specific examples of chemicals used in the chemical treatment include oxidized starch, hydroxyethyl etherified starch, enzyme-modified starch, polyacrylamide, polyvinyl alcohol, surface sizing agents, water-resistant agents, water-retaining agents, thickeners, lubricants, etc., and these can be used alone or in combination of two or more types. The above-mentioned various agents can be used by mixing with pigments. Pigments include kaolin, clay, engineered kaolin, delaminated clay, Inorganic pigments such as heavy calcium carbonate, light calcium carbonate, mica, talc, titanium dioxide, barium sulfate, calcium sulfate, zinc oxide, silicic acid, silicates, colloidal silica, and satin white, as well as organic pigments such as solid, hollow, and core-shell types, can be used alone or in combination of two or more types. The method for treating the surface of the paper substrate is not particularly limited, but known coating devices such as a rod metering size press, a pond type size press, a gate roll coater, a spray coater, a blade coater, and a curtain coater can be used. The method for producing the base paper (papermaking) is not particularly limited, and the paper base material can be produced by making paper using a known Fourdrinier former, on-top hybrid former, gap former machine, etc., using an acidic papermaking, neutral papermaking, or alkaline papermaking method.

[0095] The base paper is made from pulp and may contain fillers, various auxiliary agents, and the like. Examples of pulp that can be used include chemical pulps such as bleached hardwood kraft pulp (LBKP), unbleached hardwood kraft pulp (LUKP), bleached softwood kraft pulp (NBKP), unbleached softwood pulp (NUKP), sulfite pulp, and other such pulps; mechanical pulps such as stone-ground pulp and thermomechanical pulp; deinked pulp; and recycled paper pulp and other such wood fibers; and non-wood fibers obtained from kenaf, bamboo, hemp, and the like. One type may be used alone, or two or more types may be appropriately mixed and used. Among these, it is preferable to use chemical pulp or mechanical pulp made from wood fibers, and it is more preferable to use chemical pulp, because they are less likely to be mixed with foreign matter, less likely to discolor over time, have a high degree of whiteness, and provide a good surface feel when printed. As the filler, known fillers can be used, specific examples of which include white carbon, talc, kaolin, clay, heavy calcium carbonate, light calcium carbonate, titanium oxide, zeolite, and synthetic resin fillers. As various additives, aluminum sulfate and various anionic, cationic, nonionic or amphoteric retention aids, drainage aids, paper strength agents, internal sizing agents, etc. may be used as necessary. Furthermore, dyes, fluorescent whitening agents, pH adjusters, defoamers, pitch control agents, slime control agents, etc. may also be added as necessary.

[0096] If necessary, plastic compounding agents and additives such as lubricants, crosslinking agents, antioxidants, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, etc. can be added to the paper base material and resin used in the paper base layer for the purpose of improving or modifying processability, heat resistance, weather resistance, mechanical properties, dimensional stability, oxidation resistance, slipperiness, release properties, flame retardancy, mold resistance, electrical properties, strength, etc., and the like. The amount of these additives can be arbitrarily added depending on the purpose, as long as it does not adversely affect other performance properties.

[0097] ≪Printing layer≫ The printed layer visually presents design patterns such as letters, numbers, figures, symbols, pictures, patterns, etc. for the purpose of decoration, indication of contents, indication of expiration date, indication of manufacturer, seller, etc., and for imparting aesthetic appeal, and can form the desired design pattern. The printing layer can be provided on the surface of the paper base layer that is the outer side of the liquid paper container using a conventionally known printing ink. The printing method is not particularly limited, and conventionally known methods such as gravure printing, flexographic printing, and screen printing can be used. The printing layer may be provided on the entire surface of the printing surface, or may be provided on only a part of the surface. In order to make the printed layer visible, it is preferable that when the liquid paper container is formed, the printed layer be the outermost layer, or a layer that is outer than the printed layer be transparent.

[0098] ≪Adhesive resin layer≫ An adhesive resin layer or an anchor coat layer is included between each layer constituting the oxygen absorbing laminate. can be done. The adhesive resin layer may be, for example, a layer (extruded resin layer) formed by a (co)extrusion lamination method in which an adhesive resin composition is melt-extruded, a T-die (co)extrusion method, or the like, or may be a layer (dry laminate layer) formed by dry lamination using a dry laminate adhesive. In the present invention, among the above, the extruded resin layer is preferred. If necessary, the surface of the laminated adhesive resin layer may be subjected to a physical surface treatment such as corona discharge treatment, ozone treatment, plasma treatment, glow discharge treatment, sandblasting treatment, etc., or a chemical surface treatment such as oxidation treatment using chemicals. Examples of the resin contained in the adhesive resin composition include polyolefin resins, acid-modified polyolefin resins obtained by acid-modifying polyolefin resins by graft polymerization or copolymerization with unsaturated carboxylic acids or their anhydrides such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, fumaric acid, itaconic acid, etc., polyvinyl acetate resins, poly(meth)acrylic resins, polyvinyl chloride resins, etc. These resins can be used alone or in combination.

[0099] Specific examples of polyolefin resins include polyethylene, low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, ethylene-α-olefin copolymers polymerized using a metallocene catalyst, polypropylene, ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol copolymers, ionomer resins, ethylene-acrylic acid copolymers, ethylene-ethyl acrylate copolymers, ethylene-methacrylic acid copolymers, ethylene-methyl methacrylate copolymers, ethylene-propylene copolymers, methylpentene (co)polymers, butene (co)polymers, polyisoprene, ethylene-acrylic acid copolymers, ethylene-methacrylic acid copolymers, and cyclic olefin (co)polymers such as polynorbornene. The copolymers may be random or block copolymers. Polyolefin resins are classified into, for example, polyethylene resins and polypropylene resins depending on the skeleton of the monomer used in the synthesis of the polyolefin, and may be copolymers. In the present invention, the term "polyethylene resin" is added as a general term for various types, and for example, polyethylene resin is also used as a general term for various types of polyethylene. Polyolefins produced by polymerizing α-olefins such as ethylene, propene, 1-butene, 1,3-butadiene, and 1-hexene as raw materials are called polyethylene-based resins, polypropylene-based resins, polybutylene-based resins, polybutadiene-based resins, polyhexene-based resins, and the like, respectively.

[0100] The adhesive resin layer may contain additives such as antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, antiblocking agents, flame retardants, crosslinking agents, and colorants, as long as the additives do not impair the characteristics of the present invention. The thickness of the adhesive resin layer is not particularly limited, but in the case of an extruded resin, it is preferably 5 μm or more and 60 μm or less, and in the case of a dry lamination adhesive, it is preferably 0.1 g / m 2 More than 20g / m 2 By setting the thickness of the adhesive resin layer within the above numerical range, stable adhesive strength can be obtained. In addition, examples of the dry lamination adhesive that constitutes the adhesive resin layer formed by dry lamination include two-component curing urethane adhesives, polyester urethane adhesives, polyether urethane adhesives, acrylic adhesives, polyester adhesives, polyamide adhesives, polyvinyl acetate adhesives, epoxy adhesives, rubber adhesives, and others.

[0101] The anchor coat layer is a layer formed by applying and drying an anchor coat agent, and can improve the adhesion between adjacent layers. The anchor coating agent may be any resin having a heat resistant temperature of 135° C. or higher, such as a vinyl modified resin, an epoxy resin, a urethane resin, a polyester resin, or a polyethyleneimine. Among the above, a curable anchor coating agent that contains a polyacrylic or polymethacrylic resin (polyol) having two or more hydroxyl groups in one molecule as a base agent and an isocyanate compound as a curing agent is particularly preferred. A silane coupling agent may also be used in combination, and nitrocellulose may also be used in combination to improve heat resistance. The thickness of the anchor coat layer is not particularly limited, but is preferably, for example, 0.05 μm or more and 1 μm or less.

[0102] <Functional layer> Examples of functional layers include layers made of resins that have barrier properties against oxygen gas, water vapor, etc., and / or have low adsorption of fragrance ingredients contained in the contents to be filled and packaged, and thus have excellent aroma retention, and further have properties that do not cause changes in taste or odor, and that can be extrusion-molded, and layers made of light-shielding materials (light-shielding layers).

[0103] Specific examples of the resin that can be used include polyacrylic resins, polymethacrylic resins, polyacrylonitrile resins, polymethacrylonitrile resins, polystyrene resins, polycarbonate resins, polyethylene terephthalate resins, or resins in which a portion of the ethylene component and / or terephthalate component thereof is copolymerized or modified with other di- or higher polyhydric alcohol components or dicarboxylic acid components, or polyester resins such as polyethylene naphthalate resins, polyamide resins, saponified ethylene-vinyl acetate copolymers, polyvinyl alcohol resins, polyvinyl chloride resins, polyvinylidene chloride resins, and other resins.

[0104] Among the above-mentioned resins, it is preferable to use a resin that has aroma retention and also has barrier properties against oxygen gas or water vapor, etc., and specifically, it is preferable to use a resin that is rich in aroma retention and barrier properties, such as a saponified ethylene-vinyl acetate copolymer, a polyamide resin, a polyacrylonitrile resin, or a polyester resin.

[0105] The light-shielding layer is a layer provided to prevent ultraviolet light and / or visible light from reaching the contents. The light-shielding layer can be formed using white ink mainly composed of titanium oxide or the like, black ink mainly composed of carbon black or the like, gray ink mainly composed of aluminum paste, colorant-colored resin film made light-shielding by adding pigments or dyes or the like, metal foil, metal vapor deposition film, or the like. As described above, when a metal foil such as an aluminum foil is used as the barrier layer, the barrier layer can also function as a light-shielding layer. These light-shielding materials can be used alone or in combination of two or more. When white ink, black ink or gray ink is used, the thickness of the light-shielding layer is preferably 4 μm or more and 12 μm or less, and more preferably 5 μm or more and 9 μm or less. In the case of aluminum foil, the thickness is preferably 5 μm to 30 μm, in the case of a metal vapor deposition film, the thickness is preferably 50 Å to 3000 Å, more preferably 100 Å to 1000 Å, and in the case of a colorant-colored resin film, the thickness is preferably 5 μm to 300 μm, more preferably 10 μm to 100 μm.

[0106] <Reinforcement layer> The reinforcing layer is a layer that imparts mechanical strength, deformation resistance, drop impact resistance, pinhole resistance, heat resistance, airtightness, quality maintenance, workability, sanitation, and the like to the laminate. The reinforcing layer may be formed from any of an extrusion-formed or inflation-formed resin film, a resin coating film, synthetic paper, and the like.

[0107] Specific examples of the resin contained in the reinforcing layer include low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, polypropylene, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, ionomer resin, ethylene-ethyl acrylate copolymer, ethylene-acrylic acid or methacrylic acid copolymer, methylpentene polymer, polybutene resin, polyvinyl chloride resin, polyvinyl acetate resin, polyvinylidene chloride resin, vinyl chloride-vinylidene chloride copolymer, poly(meth)acrylic resin, polyacrylonitrile resin, polystyrene resin, acrylonitrile-styrene copolymer (AS resin), acrylonitrile-butadiene-styrene copolymer (ABS resin), polyester resin, polyamide resin, polycarbonate resin, polyvinyl alcohol resin, saponified ethylene-vinyl acetate copolymer, fluorine resin, diene resin, polyacetal resin, polyurethane resin, cellulose, nitrocellulose, and other known resins. In the present invention, it is preferable to use a polyester resin for the reinforcing layer. Examples of polyester resins include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), polybutylene naphthalate (PBN), polytetramethylene terephthalate, and polycyclohexane dimethylene terephthalate (PCT). The resin film may be either unstretched or uniaxially or biaxially stretched. The reinforcing layer may be provided with a vapor deposition film for the purpose of improving the barrier property, and may contain additives such as antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, antiblocking agents, flame retardants, crosslinking agents, and colorants, as long as the properties of the present invention are not impaired. The thickness of the reinforcing layer is not particularly limited, but is preferably 5 μm or more and 500 μm or less, and more preferably 10 μm or more and 200 μm or less.

[0108] <Method of producing oxygen-absorbing laminate for paper containers> A method for producing an oxygen absorbing laminate for paper containers using the above-mentioned materials will be described below. The production method shown below is one example and does not limit the present invention. The layers constituting the oxygen-absorbing laminate for paper containers can be laminated by any method used in the production of ordinary packaging materials, such as wet lamination, dry lamination, solventless dry lamination, extrusion lamination, T-die coextrusion molding, coextrusion lamination, inflation molding, and the like. The oxygen-absorbing laminate for paper containers of the present invention can also be subjected to secondary processing for the purpose of imparting surface functions such as chemical functions, electrical functions, magnetic functions, mechanical functions, friction / wear / lubrication functions, optical functions, thermal functions, and biocompatibility. Examples of secondary processing include embossing, painting, adhesion, printing, metallizing (plating, etc.), mechanical processing, surface treatment (antistatic treatment, corona discharge treatment, plasma treatment, photochromism treatment, physical vapor deposition, chemical vapor deposition, coating, etc.), etc. The laminate of the present invention can also be subjected to lamination (dry lamination and extrusion lamination), bag making, and other post-processing.

[0109] When the above lamination is performed, if necessary, the surface of each layer may be pretreated, for example, by corona treatment or ozone treatment. In addition, anchor coating agents such as isocyanate (urethane), polyethyleneimine, polybutadiene, and organic titanium, or lamination adhesives such as polyurethane, polyacrylic, polyester, epoxy, polyvinyl acetate, cellulose, and others may be optionally used. It can be used.

[0110] As long as the paper base layer, oxygen barrier layer, oxygen absorbing adhesive layer, and sealant layer are laminated in this order, the order in which each layer is formed and laminated may be arbitrary. For example, an example will be described in which an oxygen-absorbing laminate for a paper container having a layer structure of a paper base layer / oxygen barrier layer / oxygen-absorbing adhesive layer / sealant layer is produced. For example, first, an oxygen barrier layer is formed on the corona-treated surface of the paper base layer. Next, an oxygen-absorbing adhesive composition is applied to the laminated oxygen barrier layer, and dried as necessary to form an oxygen-absorbing adhesive layer. Then, a sealant film for the sealant layer is adhered onto the oxygen-absorbing adhesive layer to form a sealant layer. Then, an aging treatment is performed as necessary. In this manner, an oxygen-absorbing laminate for paper containers can be obtained.

[0111] <Oxygen-absorbing packaging material for paper containers> The oxygen-absorbing packaging material for paper containers is a packaging material made from the oxygen-absorbing laminate for paper containers and used for producing paper containers for liquids. The oxygen-absorbing packaging material for paper containers may further include layers having various functions, if necessary.

[0112] <Oxygen-absorbing paper container for liquids> The oxygen-absorbing paper container for liquids of the present invention is a paper container for liquids produced using the oxygen-absorbing packaging material for paper containers of the present invention. In addition, added value can be added by various shape designs and printing decorations. In one embodiment, the oxygen-absorbing paper container for liquids of the present invention has a shape as shown in Fig. 3, and a paper container 20 of the present invention comprises a body 21, a roof-like top 22 with a sloping upper surface formed at the upper open end of the body 20, and a bottom 23 formed at the lower open end of the body 21. The paper container 20 can be produced, for example, from a blank plate 24 shown in Fig. 4. In an oxygen-absorbing paper container for liquids, the oxygen barrier layer is located outside the oxygen-absorbing adhesive layer.

[0113] <Manufacturing method of oxygen-absorbing paper container for liquids> The paper container 20 can be formed, for example, by the following method. The example given below is merely one example of the method for producing the oxygen-absorbing paper container for liquids of the present invention, and the present invention is not limited thereto. First, the laminate shown in FIG. 2 is punched out to form a blank plate 24 as shown in FIG. Next, a spout part that mates with the cap is attached, folded so that the sealant layer is on the inside, heat sealed, and the cap is attached, thereby completing the manufacture of the paper container 20. In the above, the heat sealing can be performed by a known method such as bar sealing, rotary roll sealing, belt sealing, impulse sealing, high frequency sealing, ultrasonic sealing, flame sealing, etc.

[0114] The present invention will be described in more detail below with reference to examples and comparative examples. EXAMPLES

[0115] The present invention will be described in more detail with reference to the following examples and comparative examples, but the present invention is not limited to these examples.

[0116] <Raw materials> The main raw materials used in the examples are as follows: [Raw materials for oxygen absorbing compounds] Polypropylene ether diol 1: SANNIX PP-1000, manufactured by Sanyo Chemical Industries, Ltd. Number average molecular weight: 1000. Polypropylene ether diol 2: SANNIX PK-400, manufactured by Sanyo Chemical Industries, Ltd. Number average molecular weight: 400. Hydroxyl-terminated polyisoprene 1: Poly ip, manufactured by Idemitsu Kosan Co., Ltd. Number average molecular weight: 2500. ·Hydroxyl-terminated polybutadiene 1: Poly bd R15HT manufactured by Idemitsu Kosan Co., Ltd. Number average molecular weight 1200. Hydroxyl-terminated 1,2 addition polymer of 1,3-butadiene. Toluene diisocyanate 1: Coronate T-65, manufactured by Tosoh Corporation. · Oxygen absorbing compound 1: 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-inden-6-ol. · Oxidation promotion catalyst solution 1: Octope AE, manufactured by Hope Pharmaceutical Co., Ltd. A 4% ethyl acetate solution of cobalt octoate, an oxidation promotion catalyst. · Oxidation-promoting catalyst solution 2: Aceto-pe Mn(III) manufactured by Hope Pharmaceutical Co., Ltd. A 10% ethyl acetate solution of acetylacetone manganese(III), an oxidation-promoting catalyst.

[0117] [Adhesive resin layer, coating resin layer, anchor coating agent] DL Adhesive 1: Two-component curing polyester urethane adhesive manufactured by Rock Paint Co., Ltd. LDPE 1: LDPE manufactured by Japan Polyethylene Co., Ltd., Novatec LC520. Density 0.923g / cm 3 , MFR3.6g / 10min. AC agent 1: Urethane-based anchor coating agent. [Film for paper base layer, reinforcing layer, barrier layer] PET film 1: Toyobo Co., Ltd. biaxially oriented PET film, E5200. Thickness: 12 μm. · Transparent vapor-deposited PET film 1: IB-PET manufactured by Dai Nippon Printing Co., Ltd. One-sided transparent alumina vapor-deposited PET film. 12μm thick. ·Paper base material 1: basis weight 400g / m 2 Uncoated base paper manufactured by Clearwater Paper. Aluminum foil 1: 7μm thick aluminum foil.

[0118] [Printing layer ink] Gravure ink 1: SNP manufactured by Showa Ink Industrial Co., Ltd.

[0119] [Sealant layer film] LLDPE film 1: SK-L manufactured by Dai Nippon Printing Co., Ltd. Non-oriented LLDPE film 40μm thick.

[0120] <Preparation of raw material solutions> (Synthesis of polyol 1 and preparation of polyol solution 1) The following raw materials were added to a flask equipped with a nitrogen inlet tube, a stirrer, a rectification column, and a condenser, and dehydration condensation was carried out at an internal temperature of 180 to 200°C with stirring. Ethylene glycol 53.8 parts by mass Neopentyl glycol 180.3 parts by mass 1,6-Hexanediol 204.6 parts by mass Isophthalic acid 287.8 parts by mass Adipic acid 273.5 parts by mass When the acid value of the solid content of the reaction liquid reached 15 mgKOH / g, the dehydration reaction was further allowed to proceed at 200 to 240° C. while blowing in nitrogen. When the acid value of the solid content of the reaction liquid became 10 mgKOH / g or less, the internal pressure was reduced to 30 Torr and the reaction was continued. When the acid value of the solid content of the reaction liquid became 3 mgKOH / g or less, the reaction was terminated and the liquid was cooled to room temperature to obtain Polyol 1. The number average molecular weight of the resulting polyester polyol, Polyol 1, was 2,000. Next, polyol 1 was dissolved in ethyl acetate to prepare a polyol solution 1 having a solid content of 60% by mass.

[0121] (Synthesis of polyol 2 and preparation of polyol solution 2) The following raw materials were charged into a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser, and the mixture was heated with stirring to carry out a reflux reaction for 6 hours. Polypropylene ether diol 1 300.0 parts by mass Polypropylene ether diol 2 250.0 parts by mass Toluene diisocyanate 1 104.0 parts by mass Ethyl acetate 163.5 parts by mass When it was confirmed by infrared absorption spectroscopy that the absorption of the isocyanate group had completely disappeared, the synthesis was terminated and the reaction mixture was cooled to obtain polyol 2. The number average molecular weight of the resulting urethane chain extended polyol, polyol 2, was 2,000. Next, polyol 2 was dissolved in ethyl acetate to prepare a polyol solution having a solid content of 60% by mass.

[0122] (Preparation of polyisocyanate solution 1) The following raw materials were added to a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser and stirred to obtain a polyisocyanate solution 1 having a solid content of 60% by mass. Hexamethylene diisocyanate (buret form) 100.0 parts by mass Ethyl acetate 66.7 parts by mass

[0123] [Table 1]

[0124] <Synthesis of oxygen absorbing compound and preparation of oxygen absorbing compound solution> [Oxygen absorbing compound 2] First, the following raw materials were added to a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser, and the mixture was reacted at an internal temperature of 80 to 90° C. for 8 hours with stirring. Oxygen absorbing compound 1 100.0 parts by mass Isophorone diisocyanate 74.0 parts by mass When it was confirmed that the absorption of the isocyanate group had completely disappeared in the infrared absorption spectrum, the synthesis was terminated and the mixture was cooled to obtain oxygen-absorbing compound 2. Then, the oxygen-absorbing compound 2 was dissolved in ethyl acetate to prepare an oxygen-absorbing compound solution 2 having a solid content of 80 mass %.

[0125] [Oxygen absorbing compound 3] First, the following raw materials were added to a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser, and the mixture was reacted at an internal temperature of 80 to 90° C. for 8 hours with stirring. Oxygen absorbing compound 1 100.0 parts by mass Polyisocyanate solution 1 212.5 parts by weight When it was confirmed that the content of NCO groups in the solid content of the reaction liquid by the amine equivalent method reached approximately 0.64 mass %, the synthesis was terminated, the liquid was cooled, and the solvent was removed to obtain oxygen-absorbing compound 3. Then, the oxygen-absorbing compound 3 was dissolved in ethyl acetate to prepare an oxygen-absorbing compound solution 3 having a solid content of 60 mass %.

[0126] [Oxygen-absorbing compound 4] First, the following raw materials were added to a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser, and the mixture was reacted at an internal temperature of 80 to 90° C. for 8 hours with stirring. Oxygen absorbing compound 1 100.0 parts by mass Polyol solution 1 682.3 parts by mass Polyisocyanate solution 1 265.6 parts by mass When it was confirmed that the absorption of the isocyanate group had completely disappeared in the infrared absorption spectrum, the synthesis was terminated, and the mixture was cooled and the solvent was removed to obtain oxygen-absorbing compound 4. Then, the oxygen-absorbing compound 4 was dissolved in ethyl acetate to prepare an oxygen-absorbing compound solution 4 having a solid content of 60 mass %.

[0127] [Oxygen-absorbing compound 5] Oxygen absorbing compound 5 was obtained in the same manner as in the above-mentioned oxygen absorbing compound 4, except that polyol solution 2 was used instead of polyol solution 1. Then, the oxygen-absorbing compound 5 was dissolved in ethyl acetate to prepare an oxygen-absorbing compound solution 5 having a solid content of 60 mass %.

[0128] [Oxygen-absorbing compound 6] The following raw materials were charged into a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser, and the reaction was carried out for 6 hours at an internal temperature of 80 to 90°C with stirring. Hydroxyl-terminated polyisoprene 1 100.0 parts by mass Isophorone diisocyanate 4.7 parts by weight When it was confirmed by infrared absorption spectroscopy that the absorption of the isocyanate group had completely disappeared, the synthesis was terminated and the mixture was cooled to obtain oxygen-absorbing compound 6, which was a urethane polyol. The number average molecular weight of the obtained oxygen absorbing compound 6 was 7,000. Then, the oxygen absorbing compound 6 was dissolved in ethyl acetate to prepare an oxygen absorbing compound solution 6 having a solid content of 60 mass %.

[0129] Table 2 shows the composition of the reaction solution used in synthesizing oxygen-absorbing compounds 2 to 6. Moreover, the charged compositions of oxygen-absorbing compound solutions 2 to 6 are summarized in Table 3.

[0130] [Table 2]

[0131] [Table 3]

[0132] <Preparation of oxygen-absorbing adhesive composition> (Preparation of oxygen-absorbing adhesive composition A1) The following raw materials were mixed at room temperature and homogenized to obtain an oxygen-absorbing adhesive composition A1, which was then subjected to various evaluations. Oxygen absorbing compound solution 2 100 parts by mass Polyol solution 1 100 parts by weight Polyisocyanate solution 1 10 parts by weight Oxidation promoting catalyst solution 1 1 part by mass Ethyl acetate 140 parts by weight

[0133] (Preparation of oxygen-absorbing adhesive compositions A2 to A9 and B1 to B2) According to the formulations in Tables 4 and 5, oxygen-absorbing adhesive compositions A2 to A9 and B1 to B2 were obtained in the same manner as for oxygen-absorbing adhesive composition A1.

[0134] [Table 4]

[0135] [Table 5]

[0136] [Table 6]

[0137] [Example 1] On one side of the PET film 1 as a reinforcing layer, the oxygen absorbing adhesive A1 was applied in an amount of 3.0 g / m2 after drying. 2 Then, the aluminum foil for the oxygen barrier layer and the dry lamination were applied and dried so that The plates were attached by the laminate method. Then, the AC agent 1 was applied to the surface of the laminated aluminum foil 1 so that the film thickness after drying would be 0.5 μm, and then dried to form an anchor coat layer. Next, the anchor coat layer surface and the paper substrate were bonded by extrusion lamination via an adhesive resin layer made of 330°C molten LDPE1 extruded from an extruder. The thickness of the adhesive resin layer was adjusted to 25 μm. Then, the surface of the laminated paper base material 1 was extrusion coated with molten LDPE 1 at 330° C. extruded from an extruder to form a coating resin layer with a thickness of 25 μm. Next, AC agent 1 was applied to the surface of the laminated PET film 1 so as to have a film thickness after drying of 0.5 μm, and then dried to form an anchor coat layer. The anchor coat layer surface and the LLDPE film 1 for the sealant layer were then bonded together by extrusion lamination via an adhesive resin layer made of molten LDPE 1 extruded from an extrusion molding machine at 330° C. The thickness of the adhesive resin layer was adjusted to 25 μm. Next, a corona treatment was applied to the surface of the coated resin layer formed above, and a printing layer was formed using gravure ink 1 to obtain an oxygen-absorbing laminate for paper containers. Various evaluations were then carried out. Layer structure: Printing layer / coated resin layer (25 μm) / paper base layer (365 g / m 2 ) / adhesive resin layer (25μm) / Anchor coat layer (0.5μm) / Oxygen barrier layer (aluminum foil 1:7μm) / Oxygen absorbing adhesive layer (3g / m 2 ) / Reinforcement layer (12μm) / Anchor coat layer ( 0.5μm) / adhesive resin layer (25μm) / sealant layer (40μm)

[0138] [Examples 2 to 9, Comparative Examples 1 to 3] Except for changing the oxygen-absorbing adhesive composition A1 of Example 1 to any of oxygen-absorbing adhesive compositions A2 to A9, B1, B2, or DL ​​Adhesive 1 as described in Table 7, the same procedure as in Example 1 was carried out to obtain an oxygen-absorbing laminate for paper containers and evaluate it in the same manner.

[0139] [Example 10] An oxygen-absorbing laminate for paper containers was obtained in the same manner as in Example 1, except that the aluminum foil 1 for the oxygen barrier layer was replaced with a transparent vapor-deposited PET film 1 and the vapor-deposited surface was used on the oxygen-absorbing adhesive 1 side, and the same evaluation was performed. Layer structure: Printing layer / coated resin layer (25 μm) / paper base layer (365 g / m 2 ) / adhesive resin layer (25μm) / Anchor coat layer (0.5μm) / Oxygen barrier layer (PET film: 12μm / Vapor deposition layer) / Oxygen absorbing adhesive layer (3g / m 2 ) / Reinforcement layer (12μm) / Anchor core Glue layer (0.5 μm) / Adhesive resin layer (25 μm) / Sealant layer (40 μm)

[0140] [Comparative Example 4] Except for changing the oxygen-absorbing adhesive 1 to DL adhesive 1, the same procedure as in Example 10 was repeated to obtain a laminate, which was then evaluated in the same manner.

[0141] [Table 7]

[0142] <Summary of Results> The oxygen absorbing laminate for paper containers and the oxygen absorbing paper container for liquids in all the examples have excellent laminate properties. It exhibited a balance of strength, oxygen uptake and low odor. On the other hand, the laminates and paper containers for liquids of the comparative examples showed poor results in any one of lamination strength, oxygen absorption amount, and low odor properties.

[0143] <Evaluation method>

[0144] [Oxygen absorption] The obtained oxygen-absorbing laminate for paper containers was used to make a box with the sealant layer facing inside, to produce a paper container with a capacity of 200 mL. The contents storage section of the obtained container was replaced with nitrogen and then sealed. The inside of the container was filled with 1400 cc / m2 of water with a syringe relative to the inner surface area of ​​the bag. 2 The air in the content storage area was sampled with a syringe after storage in a thermostatic chamber at 25°C for 14 days, and the oxygen concentration was measured to calculate the amount of oxygen absorbed. The oxygen concentration was measured using a zirconia oxygen concentration meter (manufactured by Toray Industries, Inc.).

[0145] [Laminate strength] A 15 mm wide strip-shaped test piece was prepared from the obtained oxygen-absorbing laminate for paper containers, and the laminate strength between the layers via the oxygen-absorbing adhesive layer was measured using a tensile tester at a tensile speed of 50 mm / min.

[0146] <Odor> After measuring the amount of oxygen absorbed, the inside of the pouch was smelled and the odor was judged according to the following criteria. Note that the odor originating from the sealant layer was excluded from the judgment. Evaluation criteria: 0: Odorless 1: Faint odor 2: Weak odor 3: Moderate odor 4: Strong odor [Explanation of symbols]

[0147] 1: Oxygen-absorbing laminate for paper containers 2:Paper base layer 3: Oxygen barrier layer 4: Oxygen absorbing adhesive layer 5: Sealant layer 6: Printing layer 7: Coating resin layer 8: Adhesive resin layer 9: Anchor coat layer 10: Reinforcement layer 20: Oxygen-absorbing paper container for liquids 21: Torso 22:Top 23: Bottom 24: Blank board

Claims

1. An oxygen-absorbing laminate for a paper container for producing a liquid paper container, comprising a layer structure in which at least a paper base layer, an oxygen barrier layer, an oxygen-absorbing adhesive layer, and a sealant layer are laminated in this order, The oxygen-absorbing adhesive layer is a layer formed from an oxygen-absorbing adhesive composition, The oxygen-absorbing adhesive composition contains at least an oxygen-absorbing compound and an oxidation-promoting catalyst, The oxygen absorbing compound has one or more unsaturated five-membered rings at the terminal of the main chain of the molecule, or at the terminals of the main chain and side chain of the molecule, any bond between the five carbon atoms constituting the unsaturated five-membered ring is a carbon-carbon double bond; A monovalent and / or divalent or higher electron-donating organic group 1 is bonded to the unsaturated five-membered ring, When the number of the unsaturated five-membered ring is one, the five-membered ring or the organic group 1 has a functional group having an active hydrogen or a group in which the active hydrogen of the functional group having an active hydrogen is substituted with a monovalent organic group 2, When the number of the unsaturated five-membered rings is two or more, the unsaturated five-membered rings are bonded to each other via a divalent or higher organic group 2 which substitutes an active hydrogen of an active hydrogen group on each of the five-membered rings or the organic group 1. Oxygen absorbing laminate for paper containers.

2. A reinforcing layer is further provided between the oxygen absorbing adhesive layer and the sealant layer. The oxygen-absorbing laminate for a paper container according to claim 1 .

3. The paper base layer includes a coating resin layer on the surface. The oxygen-absorbing laminate for a paper container according to claim 1 or 2.

4. the structure of the unsaturated five-membered ring or the structure consisting of the unsaturated five-membered ring and organic group 1 is derived from one or more members selected from the group consisting of cyclopentadiene, dicyclopentadiene, norbornene, and derivatives thereof; The oxygen-absorbing laminate for a paper container according to any one of claims 1 to 3.

5. The organic group 2 includes a structural portion derived from an isocyanate-based compound, or an isocyanate-based compound and a hydroxyl group-containing compound. The oxygen-absorbing laminate for a paper container according to any one of claims 1 to 4.

6. The isocyanate compound is one or more selected from the group consisting of xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, and derivatives thereof. The oxygen-absorbing laminate for a paper container according to claim 5 .

7. the hydroxyl group-containing compound is one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof; The oxygen-absorbing laminate for a paper container according to claim 5 or 6.

8. The organic group 2 does not have a crosslinkable functional group. The oxygen-absorbing laminate for a paper container according to any one of claims 1 to 7.

9. The organic group 2 has one or more crosslinkable functional groups, the crosslinkable functional group is a hydroxyl group and / or an isocyanate group; The oxygen-absorbing laminate for a paper container according to any one of claims 1 to 7.

10. The oxygen-absorbing compound contains one or more compounds selected from the group consisting of compounds represented by the following formulas (1) to (4): The oxygen-absorbing laminate for a paper container according to any one of claims 1 to 7. 【Chemistry 1】 【Chemistry 2】 【Chemistry 3】 【Chemistry 4】 (In the formula, a to e are each a number of 1 or more, and R 1 , R 2 , R 3 Each of the above is an organic group having one or more carbon atoms, contains at least an alkylene and / or phenylene structure, and further contains a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.

11. The oxygen-absorbing compound contains a compound represented by the following formula (5): The oxygen-absorbing laminate for a paper container according to any one of claims 1 to 7. 【Chemistry 5】 (In the formula, f is a number of 0 or more, and R 4 and R 5 Each of the groups is an organic group having one or more carbon atoms and containing at least an alkylene and / or phenylene structure, and further, The polyol may include a structure derived from one or more selected from the group consisting of alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.

12. The oxidation-promoting catalyst is a peroxide or a compound containing a cation of a transition metal. The oxygen-absorbing laminate for a paper container according to any one of claims 1 to 11.

13. The compound containing a cation made of a transition metal is a metal soap made of a transition metal compound capable of releasing a cation or complex made of a transition metal and an anion or ligand made of a fatty acid. The oxygen-absorbing laminate for a paper container according to any one of claims 1 to 11.

14. The oxygen absorbing adhesive composition further contains a modifier, The modifying agent contains an isocyanate compound and / or a hydroxyl group-containing compound. The oxygen-absorbing laminate for a paper container according to any one of claims 1 to 13.

15. The isocyanate compound is one or more selected from the group consisting of xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, and derivatives thereof. The oxygen-absorbing laminate for a paper container according to claim 14.

16. the hydroxyl group-containing compound comprises one or more selected from the group consisting of polyester polyols, poly(meth)acrylic acid ester polyols, polyalkylene ether diols, and urethane chain-extended polyols thereof; The oxygen-absorbing laminate for a paper container according to claim 13 or 14.

17. An oxygen-absorbing packaging material for paper containers, produced using the oxygen-absorbing laminate for paper containers according to any one of claims 1 to 16.

18. An oxygen-absorbing paper container for liquids produced using the oxygen-absorbing packaging material for paper containers according to claim 17, The oxygen barrier layer is a layer located outside the oxygen absorbing adhesive layer. Oxygen absorbing paper container for liquids.